Exosomes as mediators of repair and immunoregulation in multiple sclerosis: a new frontier in cell-free therapy - Usamah Sayed; Baraa Mohammed Yaseen; H. Malathi; Subhashree Ray; R. Thyagarajan; Aman Shankhyan; Rasulbek Eshmetov; Zokir Ataullaev; Manoj Kumar-Mishra (Molecular Biology Reports, 2026)

Chemical composition of sedimentary organic carbon differs significantly between the intact and restored mangroves in the Philippines - R. Ray; M. Kida; R. Suwa; T. Miyajima; Charissa M. Ferrera; Rene Rollon; Yasmin H. Primavera-Tirol; Maria Lourdes San Diego-McGlone; Kazuo Nadaoka (Organic Geochemistry, 2026)

Pore compressibility in carbonate reservoirs: An experimental study and soft computing approach - Yuanyuan Wu; Kassem Jummaa; Farag M.A. Altalbawy; R. Roopashree; Shelesh Krishna Saraswat; Subhashree Ray; Prakhar Tomar; Samah Naem; Muyassar Norberdiyeva; Hadil Hussain Hamza; Aseel Smerat; Abdolali Yarahmadi Kandahari (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Experimental study and soft computing modeling of shaly oil and gas reservoir cation exchange capacity based on novel machine learning approach - Wu Xiaobin; Zyad Shaaban; R. Roopashree; Anupam Yadav; Subhashree Ray; Chandra Kant Bhardwaj; Aashna Sinha; Dilsora Abduvalieva; Prakhar Tomar; Heyder Mhohamdi; Usama S. Altimari; Aseel Smerat; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Comparative genomics analysis of aneuploidy and cellular fragmentation dynamics in mammalian embryos - R. Tippner-Hedges; J. Budrewicz; E.S. Rubin; K. Ray; B.A. Davis; M. Okovat; L. Carbone; E.S. Metcalf; S.L. Chavez (Journal of Equine Veterinary Science, 2026)

The alignment of tie vectors in the ITRF: an assessment - Pierguido Sarti; Luca Vittuari; Alessandra Borghi; Maria Alessandra Tini; Monia Negusini; Zuheir Altamimi; Jim R. Ray (Journal of Geodesy, 2026)
The tie vectors at co-location sites are required for combining the individual space geodetic solutions and computing the International Terrestrial Reference Frame. Their provision to the combination centres entails a proper and accurate alignment of the tie vector into the global geocentric frame. In order to assess the impact of different alignment strategies on the space geodetic combination, we test four alignment approaches—two similarity transformations and two transformations based on the local values of the deflection of the vertical—and focus on the residuals of the combination. Our results clearly show that the alignment strategy not only controls the orientation on the tie vector in the global frame—determining its global coordinates and components—but also impacts the magnitude of the tie vector’s combination residuals to an extent that can exceed the 1 cm level. In practice, the information carried by the same tie vector is affected by the alignment strategy—a step in the tie vectors’ production that we prove is critical and that can impact the combination of space geodetic techniques. At both sites, the alignment strategy (local topocentric to the global geocentric ITRF frame) that ensures higher consistency (i.e. smaller residuals) in the computation is the similarity transformation that makes use of all the available space geodetic reference points and no information about the DoV.

Hybridized Time Series Modeling with Machine Learning Techniques for Pomegranate Price Fluctuations - S. Vishnu Shankar; Rajeev Ranjan Kumar; Mrinmoy Ray; V. Lavanya; R. Subash (Agricultural Research, 2026)

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Hormone-optimized hypocotyl–epicotyl–cotyledonary tri-complex explant system enables efficient soybean transformation with reduced genotype dependence - J. Sushmitha; Durgeshwari Prabhakar Gadpayale; Navita Bansal; Ranjeet R. Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; Ashish Marathe; R. Dinesh Kumar; Akshay Talukdar; Giriraj Kumawat; Viswanathan Chinnusamy; et al. (Plant Cell Reports, 2026)

Beyond inflammation: siRNA strategies for precision targeting in rheumatological disorders - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Shahad Hisham Mahmood; Mahmood Jawad; Gaurav Sanghvi; Subasini Uthirapathy; R. Roopashree; Aditya Kashyap; A. Sabarivani; Subhashree Ray; Muthena Kareem (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Long-Term Remediation of the Savage River Mine Using Local Neutralising Waste Rock and Novel Flow-Through Waste Storage Facilities - Andrea R. Gerson; Stephen Kent; Bruce Hutchison; Daniel Ray; Roger St.C. Smart; Tony Ferguson (Mine Water and the Environment, 2026)

Evaluating the performance of selected CMIP6 GCMs for simulations of historical temperature over Ethiopia - Alehegn Belay Tagele; Temesgen Gashaw Tarkegn; Pieter R. van Oel; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Othoo Calvince Ouko; Daniel Berhanu; Amare Haileslassie; Abeyou W. Worqlul; Amare Bantider; et al. (Theoretical and Applied Climatology, 2026)
This study evaluates the performance of seven Global Climate Models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and their Ensemble mean in reproducing historical maximum (Tmax) and minimum (Tmin) temperatures across five agro-ecological zones (AEZs) of Ethiopia during 1995–2014. The assessment covers daily to annual time scales using observational and GCM datasets. Model performance was evaluated using Percent Bias (PBIAS), Root Mean Square Error (RMSE), and correlation coefficient (r), while the Comprehensive Rating Index (CRI) was applied for ranking. Results show substantial spatial and temporal variability in model performance. For Tmax, the Ensemble mean and EC-Earth3-veg performed best at the daily scale, while EC-Earth3-veg, MPI-ESM1-2-LR and BCC-CSM2-MR excelled at the monthly scale across most AEZs. Seasonally, top-performing models included Ensemble mean, MPI-ESM1-2-LR and MRI-ESM2-0 during Bega (October-January), EC-Earth3-veg, CNRM-CM6-1 and Ensemble mean during Belg (February-May) and CNRM-CM6-1 and MPI-ESM1-2-LR during Kiremt (June-September). For Tmin, CNRM-CM6-1, BCC-CSM2-MR and Ensemble mean ranked highest at both daily and monthly scales in most AEZs. At the annual scale, MRI-ESM2-0, Ensemble mean, MPI-ESM1-2-LR and CNRM-CM6-1 excel for Tmax, while EC-Earth3-veg, BCC-CSM2-MR and Ensemble mean lead for Tmin across most AEZs. MIROC6 consistently exhibited the weakest performance for both Tmax and Tmin across most AEZs and time periods. Thus, the Ensemble mean of all evaluated models does not consistently rank among the top three performers across all AEZs and time scales. The identified best-performing CMIP6 models provide valuable tools for assessing climate change impacts and developing region-and time-specific adaptation strategies in Ethiopia. Given the variability in GCM performance across AEZs and time scales, national or large-scale studies would benefit from using the Ensemble mean derived from the best-performing models. This study provides crucial insights into the strengths and weaknesses of different GCMs, supporting evidence-based decision-making and enhancing efforts to build climate resilience and adaptation strategies in the region.

Correction: Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Modeling impacts of climate change on blue and green water, and crop yield using SWAT + in Lake Tana sub-basin (Ethiopia) - Temesgen Gashaw Tarkegn; Pieter R. van Oel; Abebe D. Chukalla; Ram Lakhan Ray; Gebrekidan Worku Tefera; Abeyou W. Worqlul; Yihun T. Dile; Amare Haileslassie; Enyew Adgo; Amare Bantider; Meron Teferi Taye (Modeling Earth Systems and Environment, 2026)

Peripheral inflammation mediates the relationship between early life stress and alcohol use - Kaitlin R. McManus; Craig Enders; Dylan E. Kirsch; Malia Belnap; Erica N. Grodin; Lara A. Ray (Psychopharmacology, 2026)
Rationale Early life stress (ELS) is associated with an increased risk for alcohol consumption and development of alcohol use disorder (AUD). Inflammation may be a sex-dependent link between ELS and alcohol use; however, there is limited evidence to support such an association in individuals with AUD. Methods This secondary analysis utilized cross-sectional mediation to investigate the role of peripheral inflammation in the relationship between ELS and alcohol consumption (i.e., drinks per drinking day (DPDD)) in treatment-seeking individuals with AUD ( n = 99; 60 M/39 F). A cross-sectional moderated mediation analysis was conducted to test sex as a moderator in the link between ELS and inflammation for the above relationship. ELS was conceptualized as a dichotomous “no-moderate ELS” vs. “high-ELS” predictor. Results High-ELS was associated with higher inflammation (95%CI 0.039,1.558), and higher inflammation was associated with greater DPDD ( 95%CI 0.024,0.098). A mediation effect emerged where high-ELS influenced greater DPDD through elevated inflammation ( ab = 0.044, 95%CI 0.002,0.113). No direct effects between ELS and DPDD emerged (95%CI -0.177,0.108). The interaction between ELS and sex on inflammation was significant for females (95%CI: 0.304,2.719) but not males (95%CI: -0.634,1.270). The mediation relationship between ELS and DPDD through inflammation was significant for females ( ab(female) = 0.087, 95%CI: 0.013,0.199) but not males (95%CI: -0.040,0.086). Conclusions Findings suggest that ELS is associated with recent alcohol use through peripheral inflammation in treatment-seeking individuals with AUD and indicate that this pathway is sex-dependent. Inflammation may be a treatment target for individuals with AUD who have experienced ELS, especially females. Clinical Trials Registration: NCT03594435, registered July 11, 2018.

Complex Love Numbers in the Diurnal and Semidiurnal Tidal Bands Determined from Satellite Tracking and Altimetry - R. D. Ray; B. D. Loomis; K. E. Rachlin; J. J. Otero Torres (Pure and Applied Geophysics, 2026)

Mega-analysis of no-tillage and reduced tillage impacts on crop yields and greenhouse gas emissions - Lovish Kasrija; Dafeng Hui; Avedananda Ray; Wei Ren; Lixin Wang; Philip A. Fay; Douglas R. Smith; Jianwei Li; Prabodh Illukpitiya; Hanqin Tian (Field Crops Research, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

Optimized Agrobacterium-mediated CRISPR/Cas9 transformation in soybean through comparative evaluation of cotyledonary node and half-seed explants - Durgeshwari Prabhakar Gadpayale; J. Sushmita; Navita Bansal; Shalini Singh; Ch Prasanna Kumari; C. R. Nagesh; Ranjeet Ranjan Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; R. Dinesh Kumar; Arun Kumar; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Molecular regulation by ubiquitin-specific proteases (USPs) in HCC: cell cycle, oncogenic signaling, and beyond - Furqan N. Al-Khateeb; Asraa Yacoob Yousif; Sarmad Ghazi Al-Shawi; Ali G. Alkhathami; Roopashree R.; Aditya Kashyap; Deepak Nathiya; Subhashree Ray; Mohammed Jawad Alnajar; Muthana Kareem (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Permeability reduction prediction in low-salinity water flooding of clay-rich sandstones through machine learning - Yuman Li; Farag M.A. Altalbawy; Hardik Doshi; Anupam Yadav; R. Roopashree; Aditya Kashyap; Karthikeyan Jayabalan; Subhashree Ray; Dilsora Abduvalieva; Ahmad Abumalek; Guichao Liu; Mohammad R.K.M. Al-Badkubi (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Depth-dependent azimuthal seismic anisotropy governed by Couette/Poiseuille flow partitioning in the asthenosphere - Zhirui Ray Wang; Clinton P. Conrad; Sergei Lebedev; Giampiero Iaffaldano; John R. Hopper (Earth and Planetary Science Letters, 2025)

Associations between local-scale soil and tree context factors and Acute Oak Decline (AOD): plant-soil feedbacks and the cause-effect conundrum - Liz J. Shaw; Mojgan Rabiey; Mateo San José; Toni-Kim Clarke; Alice Broome; Luci J. Corbett; Oliver R. Booth; Glyn A. Barrett; Gail M. Preston; Nadia Barsoum; Karsten Schönrogge; Robert W. Jackson; et al. (Plant and Soil, 2025)
Background and aims Acute oak decline (AOD), a decline syndrome affecting mature oaks, involves bacterial pathogens which likely act as opportunists under host stress. Trees displaying symptoms (bleeding cankers) appear in localized clusters, not whole stands. This study investigates the potential involvement of local-scale factors, in interaction with large-scale environmental drivers, in influencing onset and progression of AOD. Methods AOD-symptomatic ( n = 30) and asymptomatic trees ( n = 30) across three UK oak woodlands were assessed for tree characteristics, their surrounding context, and soil properties. Results Tree health status was linked to significant differences in soil and tree properties across sites. Symptomatic trees exhibited greater loss of crown density, lower local stand (0–20 m) basal area and shallower depth to gleying. Significant differences in soil properties included lower concentrations of Olsen P, total N, and exchangeable Mg in symptomatic trees, alongside higher exchangeable Fe, especially at 40–50 cm depth. Depth to gleying and exchangeable Fe were identified as the most influential predictors of AOD. Conclusions AOD symptomatic trees may experience seasonal soil water saturation closer to the surface compared to asymptomatic trees, resulting in a higher proportion of their roots being exposed to an anoxic, iron-reducing environment. This study is the first to report such an association between gleying depth, likely seasonal water saturation, and symptom status for AOD. It is unclear whether water balance and associated soil nutrient variations are predisposing factors or consequences of declining tree health, though the identified local-scale factors likely contribute to AOD. A feedback loop is conceptualised where declining tree health worsens soil conditions, creating a negative cycle that accelerates tree decline.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

Effects of climate and sea level change on sedimentation in the eastern Bengal Fan during the late Quaternary - A. Prajith; Jyotiranjan S. Ray; Bivin G. George; K.B. Joshi; R. Bhushan; R. Bhutani; Arvind Singh (Quaternary Science Reviews, 2025)

Correction to: Infuence of real-world cue exposure and mood states on drinking: testing neurobiological models of alcohol use disorder - Lindsay R. Meredith; Wave-Ananda Baskerville; Carrie Lee; Erica N. Grodin; Kate M. Wassum; Lara A. Ray (Psychopharmacology, 2025)

Influence of real-world cue exposure and mood states on drinking: testing neurobiological models of alcohol use disorder - Lindsay R. Meredith; Wave-Ananda Baskerville; Carrie Lee; Erica N. Grodin; Kate M. Wassum; Lara A. Ray (Psychopharmacology, 2025)
Rationale Two prominent neurobiological models of addiction, the allostatic and incentive-sensitization models, have guided clinical research on alcohol use disorder (AUD). While these models are often viewed in isolation, it is plausible these theories are complimentary. Objectives Use naturalistic, daily diary reports to determine whether positive and negative mood states influence alcohol cue sensitivity in a clinical sample with AUD. Methods This is an exploratory analysis of daily diary data collected from a non-treatment seeking sample with current AUD over two weeks. Eligible adult participants ( N = 50) were enrolled in a medication trial for AUD. Each morning, participants retrospectively reported on pre-drinking mood states, alcohol cue exposure, and craving levels, and subsequent alcohol intake occurring the previous day. Multilevel models tested the singular and interactive relationships between cue exposure and mood states with craving and drinking. Within-person and between-person outcomes were assessed. Exploratory analyses examined whether individuals with withdrawal-related dysphoria were more vulnerable to mood states and cue-reactivity. Results Greater cue exposure was associated with higher daily drinking levels ( p = .001), but not daily alcohol craving. Higher negative mood ( p < .0001) and lower positive mood ( p = .012) were associated with higher daily alcohol craving, but not same-day drinking. As negative mood levels increased ( p < .01) and positive mood levels decreased ( p = .010), the relationship between cue exposure and same-day drinking became stronger. These findings were most pronounced among those with withdrawal-related dysphoria. Conclusions Findings provided concomitant support for the allostatic model and incentive-sensitization model as determinants of alcohol craving and drinking among individuals with AUD.

Emulation or Degradation? Evaluating Forest Management Outcomes in Boreal Northeastern Ontario - Jay R. Malcolm; Julee J. Boan; Justina C. Ray (Environmental Management, 2025)

Plant-derived terpenoids modulating cancer cell metabolism and cross-linked signaling pathways: an updated reviews - Pratibha Pandey; Meenakshi Verma; Gaurav Sanghvi; Roopashree R.; Kamal Kant Joshi; Kavitha V.; Subhashree Ray; Seema Ramniwas; Ajay Singh; Sorabh Lakhanpal; Fahad Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Signal detection of ferric carboxymaltose-induced serious adverse events: disproportionality analysis of FAERS and VigiBase data and systematic review of case reports - Reddikumar Reddy Galigutta; Christy Thomas; Mahesh Rathod; P. N. Hasik; R. S. Ray; Jai Prakash; Krishna Undela (European Journal of Clinical Pharmacology, 2025)

A framework for sustainable urban settlement planning: Integrating geographic information system and multi-criteria decision analysis - S. K. Ray; A. Teja; S. Chaudhary; M. H. Kumar; R. Rahul; K. Rammohan; D. Himabindu (Environment, Development and Sustainability, 2025)

Real-Time detection of sewer water levels and blockages using UHF-RFID sensors - Sundra R. Tatiparthi; Yashika G. De Costa; David Wyllie; Ray Y. Zhong; Shihu Hu; Zhiguo Yuan; Colin N. Whittaker; Wei-Qin Zhuang (Water Research, 2025)

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

A2B adenosine receptor-triggered intracellular calcium mobilization: Cell type-dependent involvement of Gi, Gq, Gs proteins and protein kinase C - Zhan-Guo Gao; Ray R. Gao; Clayton K. Meyer; Kenneth A. Jacobson (Purinergic Signalling, 2025)
Activation of PLCβ enzymes by G iβγ and G αq/11 proteins is a common mechanism to trigger cytosolic Ca 2+ increase. We and others reported that G αq/11 inhibitor FR900359 (FR) can inhibit both G αq - and, surprisingly, G iβγ -mediated intracellular Ca 2+ mobilization. Thus, the G αi -G βγ -PLCβ-Ca 2+ signaling axis depends entirely on the presence of active G αq , which reasonably explained FR-inhibited G iβγ -induced Ca 2+ release. However, the conclusion that G iβγ signaling is controlled by G αq derives mostly from HEK293 cells. Here we show that indeed in HEK293 cells both G αq/11 siRNA and G αq/11 inhibitors diminished Ca 2+ increase triggered by native G q -coupled P2Y 1 receptors, or by transfected G i -coupled A 1 - or G s -coupled A 2B adenosine receptors (ARs). However, in T24 bladder cancer cells, G i inhibitor PTX, but not G αq/11 inhibitors, FR, YM254890 (YM) or G q/11 siRNA, inhibited Ca 2+ increase triggered by native A 2B AR activation. Simultaneous inactivation of G i and G s further suppressed A 2B AR-triggered Ca 2+ increase in T24 cells. The G αq/11 inhibitor YM fully and partially inhibited endogenous P2Y 1 - and β 2 -adrenergic receptor-induced Ca 2+ increase in T24 cells, respectively. PKC activator PMA partially diminished A 2B AR-triggered but completely diminished β 2 -adrenergic receptor-triggered Ca 2+ increase in T24 cells. Neither β-arrestin1 nor β-arrestin2 siRNA affected A 2B AR-mediated Ca 2+ increase. Unlike in T24 cells, YM inhibited native A 2B AR-triggered calcium mobilization in MDA-MB-231 breast cancer cells. Thus, G αq/11 is vital for Ca 2+ increase in some cell types, but G iβγ -mediated Ca 2+ signaling can be Gα q/11 -dependent or independent based on cell type and receptor activated. Besides G proteins, PKC also modulates cytosolic Ca 2+ increase depending on cell type and receptor.

Physicochemical fractionation reveals increased soil organic carbon storage in a wolfberry orchard under cover cropping - Fang Wang; Haonan Chen; Yamiao Gao; Wenhui Li; Lizhen Zhu; Liu Yang; Ray R. Weil; Xiongxiong Nan (Plant and Soil, 2025)

Equine welfare assessment skills certification course - R. Stewart; B. Wassel; A. Best; L. Ray; B. McGonagill; B. Jackson; P. Sapp; K. Duberstein (Journal of Equine Veterinary Science, 2025)

Effects of Disturbance and Fertilisation on Plant Community Synchrony, Biodiversity and Stability Through Succession - Janette L. Davidson; Kaitlyn R. McKnight; Megan Szojka; Dustin Gannon; Nathan I. Wisnoski; Chhaya M. Werner; Maowei Liang; Eric W. Seabloom; Courtenay Ray; Melissa H. DeSiervo; Lauren G. Shoemaker (Ecology Letters, 2025)
Global change drivers alter multiple components of community composition, with cascading impacts on ecosystem stability. However, it remains largely unknown how interactions among global change drivers will alter community synchrony, especially across successional timescales. We analysed a 22‐year time series of grassland community data from Cedar Creek, USA, to examine the joint effects of pulse soil disturbance and press nitrogen addition on community synchrony, richness, evenness and stability during transient and post‐transient periods of succession. Using multiple regression and structural equation modelling, we found that nitrogen addition and soil disturbance decreased both synchrony and stability, thereby weakening the negative synchrony–stability relationship. We found evidence of the portfolio effect during transience, but once communities settled on a restructured state post‐transience, diversity no longer influenced the synchrony–stability relationship. Differences between transient and post‐transient drivers of synchrony and stability underscore the need for long‐term data to inform ecosystem management under ongoing global change.

Reduced Cerebellar Volumes Associate with P300 Amplitude Attenuation in Children with Clinical High Risk for Psychosis and Early Onset Psychosis - Hanne van der Heijden; Hesham M. Hamoda; Aliza Ray; Maria Goldman; Maya Golden; Kelsey Graber; Frank H. Duffy; Eugene D’Angelo; Borjan Gagoski; Merve Koç Yekedüz; Carter R. Petty; Jaymin Upadhyay; et al. (The Cerebellum, 2025)

Deciphering the Impact of Hyaluronic Acid Grafting Density and Molecular Weight on Paclitaxel Liposome in CD-44 Receptor Targeting - Mahendra Kumar Prajapati; Aniketh Bishnu; Satish Rojekar; Rohan Pai; Pritha Ray; Pradeep R. Vavia (Journal of Pharmaceutical Innovation, 2025)

Performances of reanalysis products in representing the temperature climatology of Ethiopia - Tazebew Abera Tadesse; Temesgen Gashaw Tarkegn; Ram Lakhan Ray; Gebrekidan Worku Tefera; Sintayehu Fetene Demessie; Alemayehu Abate Shawul; Abeyou W. Worqlul; Pieter R. van Oel; Yihun T. Dile; Abebe D. Chukalla; Amare Haileslassie; Endeg Aniley; et al. (Theoretical and Applied Climatology, 2025)

Education for sustainable development (ESD) through participatory research (PR): A systematic review - Alexa Ray R. Fernando; Gizelle P. Tajan (Journal of Cleaner Production, 2024)

Impact of land use Change on Carbon Management Index- A Study from the Foothills of Western Himalayas - Abhishek Jangir; Sarvendra Kumar; Sushil Kumar Kharia; Pooja Jangra; Prasenjit Ray; N. R. Sudhakara; Mahesh Chand Meena; Gopal Tiwari; Awani Kumar Singh; Gaurav Mishra; Rosa Francaviglia (Journal of Soil Science and Plant Nutrition, 2024)

Genomic affinity following restoration of a locally extirpated species: a case study of desert bighorn sheep in Texas - Emily A. Wright; Joseph D. Manthey; Michael R. Buchalski; Bonnie R. McKinney; David A. Ray; Caleb D. Phillips; Robert D. Bradley (Conservation Genetics, 2024)

Slaughtering processes impact microbial communities and antimicrobial resistance genes of pig carcasses - Tara N. Gaire; Carissa Odland; Bingzhou Zhang; Ilya Slizovskiy; Blake Jorgenson; Thomas Wehri; Mariana Meneguzzi; Britta Wass; Jenna Schuld; Dan Hanson; Enrique Doster; Jacob Singer; et al. (Science of The Total Environment, 2024)

Genetic and functional modulation by agonist MRS5698 and allosteric enhancer LUF6000 at the native A3 adenosine receptor in HL-60 cells - Zhan-Guo Gao; Weiping Chen; Ray R. Gao; Jonathan Li; Dilip K. Tosh; John A. Hanover; Kenneth A. Jacobson (Purinergic Signalling, 2024)
The A 3 adenosine receptor (AR) is an important inflammatory and immunological target. However, the underlying mechanisms are not fully understood. Here, we report the gene regulation in HL-60 cells treated acutely with highly selective A 3 AR agonist MRS5698, positive allosteric modulator (PAM) LUF6000, or both. Both pro- and anti-inflammatory genes, such as IL-1a, IL-1β, and NFκBIZ, are significantly upregulated. During our observations, LUF6000 alone produced a lesser effect, while the MRS5698 + LUF6000 group demonstrated generally greater effects than MRS5698 alone, consistent with allosteric enhancement. The number of genes up- and down-regulated are similar. Pathway analysis highlighted the critical involvement of signaling molecules, including IL-6 and IL-17. Important upstream regulators include IL-1a, IL-1β, TNF-α, NF-κB, etc. PPAR, which modulates eicosanoid metabolism, was highly downregulated by the A 3 AR agonist. Considering previous pharmacological results and mathematical modeling, LUF6000’s small enhancement of genetic upregulation suggested that MRS5698 is a nearly full agonist, which we demonstrated in both cAMP and calcium assays. The smaller effect of LUF6000 on MRS5698 in comparison to its effect on Cl-IB-MECA was shown in both HL-60 cells endogenously expressing the human (h) A 3 AR and in recombinant hA 3 AR-expressing CHO cells, consistent with its HL-60 cell genetic regulation patterns. In summary, by using both selective agonists and PAM, we identified genes that are closely relevant to immunity and inflammation to be regulated by A 3 AR in differentiated HL-60 cells, a cell model of neutrophil function. In addition, we demonstrated the previously uncharacterized allosteric signaling-enhancing effect of LUF6000 in cells endogenously expressing the hA 3 AR.

Changes of North Atlantic plate motion in early Paleogene driven by Icelandic plume: Insights from kinematic and stratigraphic constraints - Zhirui Ray Wang; Giampiero Iaffaldano; John R. Hopper (Earth and Planetary Science Letters, 2024)

Radish cover crop and manure alter organic carbon characteristics and improve soil physicochemical properties as well as wolfberry yields - Fang Wang; Wenhui Li; Yamiao Gao; Lizhen Zhu; Haonan Chen; Liu Yang; Ray R. Weil; Tiannan Wang; Xiongxiong Nan (Agriculture, Ecosystems & Environment, 2024)

Leveraging meta-regression to test if medication effects on cue-induced craving are associated with clinical efficacy - Steven J. Nieto; Han Du; Lindsay R. Meredith; Suzanna Donato; Molly Magill; Lara A. Ray (Psychopharmacology, 2024)
Rationale The alcohol cue exposure paradigm is a common method for evaluating new treatments for alcohol use disorder (AUD); however, it is unclear if medication-related reductions in cue-induced craving in the human laboratory can predict the clinical success of those medications in reducing alcohol consumption during clinical trials. Objectives To use a novel meta-analytic approach to test whether medication effect sizes on cue-induced alcohol craving are associated with clinical efficacy in clinical trials. Method We searched the literature for medications tested for AUD treatment using both the alcohol cue-reactivity paradigm and randomized clinical trials (RCTs). For alcohol cue-reactivity studies, we computed medication effect sizes for cue-induced alcohol craving (k = 36 studies, 15 medications). For RCTs, we calculated medication effect sizes for heavy drinking and abstinence (k = 139 studies, 19 medications). Using medication as the unit of analysis, we applied the Williamson-York bivariate weighted least squares estimation to account for errors in both independent and dependent variables. We also conducted leave-one-out cross validation simulations to examine the predictive utility of cue-craving medication effect sizes on RCT heavy drinking and abstinence endpoints. Results There was no significant relationship between medication effects on cue-induced alcohol craving in the human laboratory and medication effects on heavy drinking ( $$\widehat{β }$$ β ^ = 0.253, SE = 0.189, p = 0.090) and abstinence ( $$\widehat{β }$$ β ^ = 0.829, SE = 0.747, p = 0.133) in RCTs. Conclusions The preliminary results of the current study challenge the assumption that alcohol cue-reactivity alone can be used as an early efficacy indicator for AUD pharmacotherapy development. These findings suggest that a wider range of early efficacy indicators and experimental paradigms be considered for Phase II testing of novel compounds.

Mixed-Method Heat Acclimation Induces Heat Adaptations in International Triathletes Without Training Modification - Carl A. James; Ashley G. B. Willmott; C. W. Daniel Lee; T. K. Gabriel Pun; Ray Tai; Oliver R. Gibson (Journal of Science in Sport and Exercise, 2024)
Purpose Heat acclimation (HA) kinetics often necessitates that the intervention is conducted in the weeks immediately preceding athletic competitions, potentially interfering with a training taper. Therefore, we investigated the efficacy of a mixed-method HA protocol, superimposed over planned external training loads, during the 3-weeks prior to the 2022 U23 World Triathlon Championships. Methods Six international triathletes completed 8 pre-competition HA sessions (5 active: running/cycling, 3 passive: hot water immersion [HWI]), across 2-weeks. Outdoor high-intensity training sessions were followed by 30–60 min HWI, whilst low-intensity cycling/running sessions were completed in a hot, humid environmental chamber. To assess heat adaptations, participants completed three 25 min heat stress tests (HST) involving iso-speed treadmill running (session 1 = HST1, session 5 = HST2, and session 8 = HST3). Physiological, haematological and wellbeing monitoring were conducted throughout HA. Results Reduced heart rate (~ − 6 beats/min) was observed within HST3 ( P = 0.01, η p 2 = 0.64), versus HST1 and HST2. No changes in core temperature were observed across HSTs ( P = 0.055 , η p 2 = 0.44). Sweat sodium concentration was lower by HST2 at the arm (− 23 ± 16 mmol/L, P = 0.02) and back (− 27 ± 17 mmol/L, P = 0.01). White blood cell count reduced from baseline to the end of HA ( P = 0.02, η p 2 = 0.27), but no changes were found in any other haematological markers (all P > 0.05). Perceptual wellbeing measures did not change across HA (all P > 0.05). Conclusion By HST3, seven prior mixed-method HA sessions improved markers of heat adaptation (exercising HR and sweat concentration) within international triathletes. Mixed-method HA may be implemented without modifying training load, with no apparent detrimental effects on athlete health or training stress markers.

Calculating Nitrogen Uptake Rates in Forests: Which Components Can Be Omitted, Simplified, or Taken from Trait Databases and Which Must Be Measured In Situ? - Ray Dybzinski; Ella Segal; M. Luke McCormack; Christine R. Rollinson; Rosemary Mascarenhas; Perry Giambuzzi; Jamilys Rivera; Lucien Fitzpatrick; Caylin Wiggins; Meghan G. Midgley (Ecosystems, 2024)

Morpho-cultural and molecular variability in Rhizoctonia solani isolates from rice-vegetable cropping alluvial zone of West Bengal - Krishna Ray; Sujit Kumar Ray; Subrata Dutta; Ashis Roy Barman; Shikha Pathak; Tasvina R. Borah (Indian Phytopathology, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Identification of QTLs for symbiotic nitrogen fixation and related traits in a soybean recombinant inbred line population - C. Bennet Krueger; Jeffery D. Ray; James R. Smith; Arun Prabhu Dhanapal; Muhammad Arifuzzaman; Fei Gao; Felix B. Fritschi (Theoretical and Applied Genetics, 2024)

Climatological features of rapidly intensifying tropical cyclones in the North Indian Ocean - Manish R. Ranalkar; Ram Kumar Giri; Kamaljit Ray (International Journal of Climatology, 2024)
The study investigates the climatological variation of rapidly intensifying tropical cyclones (RITCs) developed in the North Indian Ocean (NIO) using observational and reanalysis data from 1982 to 2020. The analysis reveals that out of 153 tropical cyclones (TC) developed in the NIO, 59 TCs underwent rapid intensification (RI). The monthly variation of RITCs exhibited bimodal distribution with a primary peak in November and a secondary peak in May. The percentage of RITCs during April–June is higher as compared to October–December. The study identifies the core zones of RI initiation in the Arabian Sea (AS) and the Bay of Bengal (BoB), respectively. The occurrences of RITCs over the AS have been observed to increase since 2000. Over 65% of RITCs occurred within 12 h of TC formation, and the duration of RI varies from 24 to 48 h. TCs with lifetime maximum intensity (LMI) less than 55 kt have not undergone RI. The trend in the 95th percentile of 24‐h intensity changes is positive but insignificant ( p ‐value >0.05) in the AS, and for the BoB, it is negative and significant ( p ‐value

Anti-inflammatory and antiproliferative activity of Helichrysum odoratissimum Sweet. against lung cancer - Tenille Esmear; Danielle Twilley; Velaphi Clement Thipe; Kattesh V. Katti; Vusani Mandiwana; Michel Lonji Kalombo; Suprakas Sinha Ray; Rirhandzu Rikhotso-Mbungela; Venugopal Reddy Bovilla; SubbaRao Madhunapantula; Lenka Langhanshova; Catarina Roma-Rodrigues; et al. (South African Journal of Botany, 2024)

Soil texture, fertilization, cover crop species and management affect nitrous oxide emissions from no-till cropland - Nathan Sedghi; Michel Cavigelli; Ray R. Weil (Science of The Total Environment, 2024)

A test of trade-offs in dispersal and reproduction within and between a sister species pair of specialist insect herbivores - Amy M. Roush; Linyi Zhang; Glen Ray Hood; James R. Ott; Scott P. Egan (Oecologia, 2024)

Evaluating the Development and Application of Stand Density Index for the Management of Complex and Adaptive Forests - Emmerson Chivhenge; David G. Ray; Aaron R. Weiskittel; Christopher W. Woodall; Anthony W. D’Amato (Current Forestry Reports, 2024)

Effect of dietary phytase on water and fecal prokaryotic and eukaryotic microbiomes in a hybrid tilapia (Oreochromis aureus x O. niloticus) mixotrophic biofloc production system - Candis L. Ray; Jason W. Abernathy; Bartholomew W. Green; Adam R. Rivers; Kevin K. Schrader; Steven D. Rawles; Matthew E. McEntire; Miles D. Lange; Carl D. Webster (Aquaculture, 2024)

Identification of Suitable Sites for Water Harvesting Structures in Jamsholaghat Sub-basin Using GIS and Multi-Criteria Decision Analysis - S. K. Ray; V. R. Desai (Journal of the Indian Society of Remote Sensing, 2024)

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

Offsets in tide-gauge reference levels detected by satellite altimetry: ten case studies - R. D. Ray; M. J. Widlansky; A. S. Genz; P. R. Thompson (Journal of Geodesy, 2023)
Comparing measurements of absolute sea level by satellite altimetry and relative sea level by a tide gauge can reveal errors in either measurement system. Combining the measurements can determine vertical land motion (VLM) at the tide gauge. We here discuss ten case studies in which a tide gauge has likely experienced a small ( $$\le 10$$ ≤ 10 cm), discontinuous offset in the vertical, suggesting inadvertent loss of reference-level stability. Proper interpretation of offsets is helped if independent VLM measurements from nearby geodetic stations are available. In two cases, earthquake-induced VLM cannot be ruled out, although it appears unlikely. Offsets as small as 1–2 cm can be detected when both altimeter and tide gauge successfully observe the same ocean signal. This is most likely to occur for tide gauges located on small, open-ocean islands. Tide gauges near large land masses are typically more challenging owing to inadequacies of satellite altimetry near land and to differences between coastal and open-ocean sea levels. The case studies highlight the utility of satellite altimetry for tide-gauge quality control.

Are medication effects on subjective response to alcohol and cue-induced craving associated? A meta regression study - Lara A. Ray; Steven J. Nieto; Lindsay R. Meredith; Elizabeth Burnette; Suzanna Donato; Molly Magill; Han Du (Psychopharmacology, 2023)
Rationale Alcohol administration and cue-reactivity paradigms are frequently used to screen for the initial efficacy of medications for alcohol use disorder (AUD). While medication effects on the primary outcomes for these paradigms are assumed to be qualitatively related, there is a critical lack of quantitative evidence to support this hypothesis. Objectives The study aims to test the relationship between medication effect sizes on subjective response to alcohol administration and medication effect sizes for cue-induced craving to cue exposure, using meta-analysis. Methods Systematic literature searches were conducted to identify randomized trials, wherein AUD medications were tested using the alcohol administration and/or cue-reactivity paradigms. From these studies, descriptive statistics were collected to compute medication effect sizes on the primary outcomes for each respective paradigm. With medication as the unit of analysis, medication effect sizes in alcohol administration studies were compared with medication effect sizes in cue-reactivity studies using the Williamson-York regression which allows for meta-regression across independent samples. Results Medication effect sizes on alcohol-induced stimulation and alcohol-induced craving were not significantly associated with medication effect sizes on cue-induced alcohol craving ( k stimulation = 10 medications, $$\widehat{β }=0.272 \left(SE=0.263\right), p=0.150$$ β ^ = 0.272 SE = 0.263 , p = 0.150 and k craving = 11 medications, $$\widehat{β }=0.217$$ β ^ = 0.217 (SE = 0.237), $$p=0.181$$ p = 0.181 ), respectively. Medication effect sizes on alcohol-induced sedation were significantly associated with medication effects on cue-induced craving ( k = 10 medications, $$\widehat{β }=-0.600$$ β ^ = - 0.600 (SE = 0.258), $$p=0.010$$ p = 0.010 ), such that medications that increased alcohol-induced sedation were more likely to reduce cue-induced alcohol craving. Conclusions With the exception of alcohol-induced sedation, there is little quantitative evidence of medication effects on subjective response domains measured during alcohol administration parallel medication effects on cue-induced alcohol craving. To provide additional context to the current study, future work should examine whether cue-reactivity findings predict clinical trial outcomes.

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Characterizing state‐managed and unmanaged fisheries in coastal marine states and territories of the United States - Michael C. Melnychuk; Charmane E. Ashbrook; Richard J. Bell; Lyall Bellquist; Kate Kauer; Jono R. Wilson; Ray Hilborn; Jay Odell (Fish and Fisheries, 2023)
The status of federally managed fisheries in the United States is well monitored, but the condition of other marine fisheries, whether state‐managed, territory‐managed or unmanaged, is less understood and often unknown. We used expert surveys to characterize the management systems of non‐federally managed fisheries in US coastal marine states and overseas territories. For 311 fisheries, we estimated an overall Fisheries Management Index (FMI) and a qualitative stock status score. These measures were positively correlated, and while a wide range of research, management, enforcement and socioeconomic criteria were partially met (FMI ≥ 0.5) for 66% of fisheries, stock status was considered as partially acceptable (score ≥ 0.5) for only 45% of fisheries and acceptable (score = 1) for only 16% of fisheries. Higher FMI was typically observed in fisheries with greater commercial landed weight, value, or greater recreational catches. Fisheries from continental states had higher FMI than those from overseas territories. Invertebrates and diadromous fish species had higher FMI on average compared to those of marine fishes. Extrapolating results for surveyed fisheries to nearly 2000 non‐federally managed US fisheries while stratifying by state and importance designation (based on commercial, recreational, cultural or ecological importance), we estimate a mean overall FMI of 0.48, and estimate that only 19% of fisheries have a reliable estimate of stock status available; both measures are lower than similar estimates for federally managed fisheries. Funding or capacity constraints and information or data limitations were identified as common challenges faced by state agencies in managing fisheries under their jurisdiction.

Structure and composition of natural ferrihydrite nano-colloids in anoxic groundwater - Maya Engel; Vincent Noël; Samuel Pierce; Libor Kovarik; Ravi K. Kukkadapu; Juan S. Lezama Pacheco; Odeta Qafoku; J. Ray Runyon; Jon Chorover; Weijiang Zhou; John Cliff; Kristin Boye; et al. (Water Research, 2023)

World Association for the Advancement of Veterinary Parasitology (W.A.A.V.P.) guideline for diagnosing anthelmintic resistance using the faecal egg count reduction test in ruminants, horses and swine - Ray M. Kaplan; Matthew J. Denwood; Martin K. Nielsen; Stig M. Thamsborg; Paul R. Torgerson; John S. Gilleard; Robert J. Dobson; Jozef Vercruysse; Bruno Levecke (Veterinary Parasitology, 2023)

Modelling crop yield and harvest index: the role of carbon assimilation and allocation parameters - Hector Camargo-Alvarez; Robert J. R. Elliott; Stefan Olin; Xuhui Wang; Chenzhi Wang; Deepak K. Ray; Thomas A. M. Pugh (Modeling Earth Systems and Environment, 2023)
Crop yield improvement during the last decades has relied on increasing the ratio of the economic organ to the total aboveground biomass, known as the harvest index (HI). In most crop models, HI is set as a parameter; this empirical approach does not consider that HI not only depends on plant genotype, but is also affected by the environment. An alternative is to simulate allocation mechanistically, as in the LPJ-GUESS crop model, which simulates HI based on daily growing conditions and the crop development stage. Simulated HI is critical for agricultural research due to its economic importance, but it also can validate the robust representation of production processes. However, there is a challenge to constrain parameter values globally for the allocation processes. Therefore, this paper aims to evaluate the sensitivity of yield and HI of wheat and maize simulated with LPJ-GUESS to eight production allocation-related parameters and identify the most suitable parameter values for global simulations. The nitrogen demand reduction after anthesis, the minimum leaf carbon to nitrogen ratio (C:N) and the range of leaf C:N strongly affected carbon assimilation and yield, while the retranslocation of labile stem carbon to grains and the retranslocation rate of nitrogen and carbon from vegetative organs to grains after anthesis mainly influenced HI. A global database of observed HI for both crops was compiled for reference to constrain simulations before calibrating parameters for yield against reference data. Two high- and low-yielding maize cultivars emerged from the calibration, whilst spring and winter cultivars were found appropriate for wheat. The calibrated version of LPJ-GUESS improved the simulation of yield and HI at the global scale for both crops, providing a basis for future studies exploring crop production under different climate and management scenarios.

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Cytogenetic Diversity in Scilloideae (Asparagaceae): a Comprehensive Recollection and Exploration of Karyo-Evolutionary Trends - Sayantani Nath; Sayantika Sarkar; Sayali D. Patil; Partha Sarathi Saha; Manoj M. Lekhak; Sudipta Ray; Satyawada Rama Rao; S. R. Yadav; R. C. Verma; Manoj K. Dhar; S. N. Raina; Sumita Jha (The Botanical Review, 2023)

The role of adaptive capacity in incremental and transformative adaptation in three large U.S. Urban water systems - Lisa Dilling; Meaghan E. Daly; William R. Travis; Andrea J. Ray; Olga V. Wilhelmi (Global Environmental Change, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Assessment of extreme rainfall through statistical process control-I chart - N S Abeysingha; K M Kularathna; A M K R Bandara; Ram L Ray (Journal of Earth System Science, 2023)

Getting the most out of maths: How to coordinate mathematical modelling research to support a pandemic, lessons learnt from three initiatives that were part of the COVID-19 response in the UK - Ciara E. Dangerfield; I. David Abrahams; Chris Budd; Matt Butchers; Michael E. Cates; Alan R. Champneys; Christine S.M. Currie; Jessica Enright; Julia R. Gog; Alain Goriely; T. Déirdre Hollingsworth; Rebecca B. Hoyle; et al. (Journal of Theoretical Biology, 2023)

A GIS-based Spatial Prediction of Landslide Hazard Zones and Mapping in an Eastern Himalayan Hilly Region Using Large Scale Soil Mapping and Analytical Hierarchy Process - R. Srinivasan; D. Vasu; S. Amar Suputhra; Rajendra Hegde; S. K. Ray; S. K. Singh (Journal of the Indian Society of Remote Sensing, 2022)

HPV Vaccine Intent among Adult Women Receiving Care at Community Health Centers - M. L. Hecht; R. BeLue; A. Ray; S. Hopfer; M. Miller-Day; F. Mckee (Journal of Cancer Education, 2022)

Early life history of the middling thread herring ( Opisthonema medirastre ) in the central Galápagos Islands - Jose R. Marin Jarrin; Solange Andrade‐Vera; Carla Brito; Lana Ray; Michelle A. Schuiteman (Journal of Fish Biology, 2022)
The authors estimated life‐history parameters of a clupeid forage fish, Opisthonema medirastre , by sampling juveniles over the course of a year in the central region of the Galápagos Islands, Ecuador. They collected 160 juveniles on the south coast of Santa Cruz Island during the wet/warm season that were 16–48 mm standard length, were 30–88 days old, had hatched at the beginning of the wet/warm season and had grown at 0.4 mm day −1 . The results suggest that in Galápagos, O . medirastre reproduce during the wet/warm season mostly under neutral ENSO conditions.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Applying Quantitative Radiographic Image Markers to Predict Clinical Complications After Aneurysmal Subarachnoid Hemorrhage: A Pilot Study - Gopichandh Danala; Masoom Desai; Bappaditya Ray; Morteza Heidari; Sai Kiran R. Maryada; Calin I. Prodan; Bin Zheng (Annals of Biomedical Engineering, 2022)

Disorders of Tetrahydrobiopterin Metabolism: Experience from South India - Somdattaa Ray; Hansashree Padmanabha; Vykuntaraju K. Gowda; Rohan Mahale; Rita Christopher; Shruthy Sreedharan; Debjyoti Dhar; Mahesh Kamate; Madhu Nagappa; Maya Bhat; Rammurthy Anjanappa; Gautham Arunachal; et al. (Metabolic Brain Disease, 2022)

Valorization of waste potato peel as iron adsorbent and catalyst in photo-oxidation: a sustainable waste management strategy - P. Dey; R. Koijam; S. Ray (International Journal of Environmental Science and Technology, 2022)

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Progress and Challenges in Earth Observation Data Applications for Agriculture at Field Scale in India and Small Farm Holdings Regions - Shibendu Shankar Ray; Vinay Kumar Dadhwal; Ranganath R. Navalgund (Journal of the Indian Society of Remote Sensing, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evaluating Connections Between Nitrogen Cycling and the Macrofauna in Native Oyster Beds in a New England Estuary - S. G. Ayvazian; Nicholas E. Ray; Anna Gerber-Williams; Sinead Grabbert; Adam Pimenta; Boze Hancock; Donald Cobb; Charles Strobel; R. W. Fulweiler (Estuaries and Coasts, 2022)

Lunar feldspathic meteorite Dhofar 081: Petrochemical constraints on petrogenesis - Dwijesh Ray; Saumitra Misra; David R Nelson (Journal of Earth System Science, 2021)

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Breeding latitude is associated with the timing of nesting and migration around the annual calendar among Purple Martin (Progne subis) populations - L. R. Neufeld; S. Muthukumarana; J. D. Fischer; J. D. Ray; J. Siegrist; K. C. Fraser (Journal of Ornithology, 2021)

Removal of textile dyes from water by jute stick activated carbon: process optimization and isotherm studies - R. K. Ghosh; D. P. Ray; A. Tewari; I. Das (International Journal of Environmental Science and Technology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Active and weakening MJO events in the Maritime Continent - Bradford S. Barrett; Casey R. Densmore; Pallav Ray; Elizabeth R. Sanabia (Climate Dynamics, 2021)
To better understand the Madden–Julian Oscillation (MJO) in the Maritime Continent (MC), events from 1980 to 2019 were classified as active or weakening according to propagation characteristics and amplitude changes in two leading indices, the Real-time Multivariate MJO (RMM) index and Outgoing Longwave Radiation (OLR) MJO Index (OMI). Active MJO events had larger index amplitudes than weakening events, and those amplitude differences appeared at day − 3 in the RMM and day − 8 in the OMI and remained through day + 15 in both indices (day 0 marked the day an event entered the MC). Thus, active events were stronger than weakening events as they approached and crossed the MC. To understand differences in environments between these events, composites of OLR and specific humidity were compared for each. Active MJO events had consistently more negative OLR anomalies and greater specific humidity in both the boundary layer and free troposphere than weakening MJO events. Those differences persisted during both easterly and westerly phases of the Quasi-biennial Oscillation (QBO) and during La Niña and El Niño. Active MJO events during QBO westerly winds had more specific humidity than active events did during QBO easterly winds. Finally, both active and weakening MJO events featured a diurnal cycle of lower-tropospheric specific humidity over land areas of the MC, and the amount of atmospheric moisture available to active events was consistently greater than weakening ones. These results indicate that index amplitude, OLR, and tropospheric specific humidity can all be important tools in identifying active and weakening MJO events in the MC, including for different phases of the QBO and the El Niño-Southern Oscillation (ENSO).

Was historical cisco Coregonus artedi yield consistent with contemporary recruitment and abundance in Lake Superior? - Benjamin J. Rook; Michael J. Hansen; Cory A. Goldsworthy; Bradley A. Ray; Owen T. Gorman; Daniel L. Yule; Charles R. Bronte (Fisheries Management and Ecology, 2021)
Historically, cisco Coregonus artedi Lesueur was the predominant prey fish and target of commercial fisheries throughout Lake Superior, but most spawning stocks collapsed by the mid‐1900s. Stocks partially recovered by the early 1990s, but contemporary abundance is considered to be below historical levels and driven by intermittent recruitment. Stochastic, age‐structured simulation models were used to determine whether historical (pre‐1955) cisco yield in Lake Superior was consistent with contemporary (1992–2015) abundance, life‐history characteristics and recruitment dynamics. When compared to contemporary stocks, the findings suggest historical stocks had: (1) similar recruits per spawner at low spawning stock sizes; (2) lower rates of compensatory density dependence; (3) similar or lower recruitment variation depending on the area and (4) higher median adult and age‐1 density. These findings are consistent with the hypothesis that eutrophication during the historical period supported greater recruitment and adult abundance and that re‐oligotrophication during the contemporary period may be limiting full recovery.

Seasonal occurrence and sexual segregation of great white sharks Carcharodon carcharias in Mossel Bay, South Africa - Hannah R. Milankovic; Nicholas D. Ray; Louise K. Gentle; Christo Kruger; Esther Jacobs; Craig J. Ferreira (Environmental Biology of Fishes, 2021)
The seasonal occurrence and temporal sexual segregation of great white sharks Carcharodon carcharias have been widely documented in various temperate and sub-tropical waters across the globe. Yet, there is limited understanding of the relationship between the life stages and habitat use of C. carcharias , particularly in the Southern Cape. In this study, we investigated the population dynamics of C. carcharias in Mossel Bay, South Africa, between 2009 and 2013, using skipper logbooks and citizen research data obtained by a cage-diving vessel. A total of 3064 sharks, ranging in life history stages from young-of-the-year to subadult, were sighted during 573 trips. Juveniles dominated the sightings throughout the study, and there was marked sexual segregation, with females dominating the total sightings of sharks. C. carcharias were most abundant during the cooler, winter season, with females differing in abundance seasonally and males maintaining a low abundance throughout the year but peaking in the winter. In addition, sea surface temperature was the best indicator of C. carcharias presence. Abundance was greatest when vertical water visibility exceeded 3 m, with cloud cover influencing overall abundance negatively. Likely reasoning for the aggregation of C. carcharias in Mossel Bay includes the favourable conditions and abundance of food. Juvenile sharks may also utilise this area as a training ground to learn from larger conspecifics. This research demonstrates that information on population size and structure of C. carcharias can be obtained effectively through a compilation of logbook and citizen science data to assess and identify potential critical habitats in the quest to develop appropriate management strategies. This research also shows value in commercial cage-diving operations deriving international data sets needed to assess global populations of C. carcharias .

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Correction to: Efficient antileishmanial activity of amphotericin B and piperine entrapped in enteric coated guar gum nanoparticles - Lipika Ray; R. Karthik; Vikas Srivastava; Sheelendra Pratap Singh; A. B. Pant; Neena Goyal; Kailash C. Gupta (Drug Delivery and Translational Research, 2021)

Efficient antileishmanial activity of amphotericin B and piperine entrapped in enteric coated guar gum nanoparticles - Lipika Ray; R. Karthik; Vikas Srivastava; Sheelendra Pratap Singh; A. B. Pant; Neena Goyal; Kailash C. Gupta (Drug Delivery and Translational Research, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Mapping quantitative trait loci (QTL) for plant nitrogen isotope ratio (δ15N) in soybean - Sumandeep K. Bazzer; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Euphytica, 2020)

Risk chart for identification of potential landslide due to the presence of residual soil - Arunava Ray; R. E. S. Chaitanya Kumar; Rajesh Rai; Suprakash Gupta (Natural Hazards, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Identification of quantitative trait loci for carbon isotope ratio (δ13C) in a recombinant inbred population of soybean - Sumandeep K. Bazzer; Avjinder S. Kaler; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Theoretical and Applied Genetics, 2020)

Identification and genotypic characterization of porcine teschovirus from selected pig populations in India - Pradeep K. Ray; P. A. Desingu; R. Anoopraj; R. K Singh; G. Saikumar (Tropical Animal Health and Production, 2020)

Role of the tumor microenvironment in regulating the anti-metastatic effect of KISS1 - Sitaram Harihar; Srijit Ray; Samyukta Narayanan; Anirudh Santhoshkumar; Thuc Ly; Danny R. Welch (Clinical & Experimental Metastasis, 2020)

Cellular and molecular mechanisms of curcumin in prevention and treatment of disease - Sita Sharan Patel; Ashish Acharya; R. S. Ray; Ritesh Agrawal; Ramsaneh Raghuwanshi; Priyal Jain (Critical Reviews in Food Science and Nutrition, 2020)

Bioaccumulation of vanadium (V), niobium (Nb) and tantalum (Ta) in diverse mangroves of the Indian Sundarbans - R. Ray; B. Dutta; S. K. Mandal; A. G. González; O. S. Pokrovsky; T. K. Jana (Plant and Soil, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Selectivity Enhancement of Paclitaxel Liposome Towards Folate Receptor-Positive Tumor Cells by Ligand Number Optimization Approach - Mahendra Kumar Prajapati; Aniketh Bishnu; Pritha Ray; Pradeep R. Vavia (AAPS PharmSciTech, 2019)

Water Column Effects on In Situ Spectral Signatures of Coral Species from Gujarat Coast, India - Nandini Ray Chaudhury; Ashwin Gujrati; T. V. R. Murthy (Journal of the Indian Society of Remote Sensing, 2019)

Early life social and ecological determinants of global DNA methylation in wild spotted hyenas - Zachary M. Laubach; Christopher D. Faulk; Dana C. Dolinoy; Luke Montrose; Tamara R. Jones; Donna Ray; Malit O. Pioon; Kay E. Holekamp (Molecular Ecology, 2019)
Environmental factors early in life can have lasting influence on the development and phenotypes of animals, but the underlying molecular modifications remain poorly understood. We examined cross‐sectional associations among early life socioecological factors and global DNA methylation in 293 wild spotted hyenas ( Crocuta crocuta ) in the Masai Mara National Reserve, Kenya, grouped according to three age classes (cub, subadult and adult). Explanatory variables of interest included annual maternal rank based on outcomes of dyadic agonistic interactions, litter size, wild ungulate prey density and anthropogenic disturbance in the year each hyena was born based on counts of illegal livestock in the Reserve. The dependent variable of interest was global DNA methylation, assessed via the LUminometric Methylation Assay, which provides a percentage methylation value calculated at CCGG sites across the genome. Among cubs, we observed approximately 2.75% higher CCGG methylation in offspring born to high‐ than low‐ranking mothers. Among cubs and subadults, higher anthropogenic disturbance corresponded with greater %CCGG methylation. In both cubs and adults, we found an inverse association between prey density measured before a hyena was 3 months old and %CCGG methylation. Our results suggest that maternal rank, anthropogenic disturbance and prey availability early in life are associated with later life global DNA methylation. Future studies are required to understand the extent to which these DNA methylation patterns relate to adult phenotypes and fitness outcomes.

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Radiological Estimation of Intracranial Blood Volume and Occurrence of Hydrocephalus Determines Stress-Induced Hyperglycemia After Aneurysmal Subarachnoid Hemorrhage - Joshua A Santucci; Stephen R Ross; John C Greenert; Faranak Aghaei; Lance Ford; Kimberly M Hollabaugh; Benjamin O Cornwell; Dee H Wu; Bin Zheng; Bradley N Bohnstedt; Bappaditya Ray (Translational Stroke Research, 2019)

Beneficial Changes in Capsicum frutescens Due to Priming by Plant Probiotic Burkholderia spp. - Rohini Sabu; R. Aswani; K. S. Nidheesh; J.G. Ray; A. Remakanthan; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Probing the effect of a room temperature ionic liquid on phospholipid membranes in multilamellar vesicles - S. Mitra; D. Ray; G. Bhattacharya; R. Gupta; D. Sen; V. K. Aswal; S. K. Ghosh (European Biophysics Journal, 2019)

Alteration in branchial NKA and NKCC ion-transporter expression and ionocyte distribution in adult hilsa during up-river migration - Soumi Dutta; Saumya Kanti Ray; G. H. Pailan; V. R. Suresh; Subrata Dasgupta (Journal of Comparative Physiology B, 2019)

Atmospheric histories, growth rates and solubilities in seawater and other natural waters of the potential transient tracers HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116 - Pingyang Li; Jens Mühle; Stephen A. Montzka; David E. Oram; Benjamin R. Miller; Ray F. Weiss; Paul J. Fraser; Toste Tanhua (Ocean Science, 2019)
We present consistent annual mean atmospheric histories and growth rates for the mainly anthropogenic halogenated compounds HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116, which are all potentially useful oceanic transient tracers (tracers of water transport within the ocean), for the Northern and Southern Hemisphere with the aim of providing input histories of these compounds for the equilibrium between the atmosphere and surface ocean. We use observations of these halogenated compounds made by the Advanced Global Atmospheric Gases Experiment (AGAGE), the Scripps Institution of Oceanography (SIO), the Commonwealth Scientific and Industrial Research Organization (CSIRO), the National Oceanic and Atmospheric Administration (NOAA) and the University of East Anglia (UEA). Prior to the direct observational record, we use archived air measurements, firn air measurements and published model calculations to estimate the atmospheric mole fraction histories. The results show that the atmospheric mole fractions for each species, except HCFC-141b and HCFC-142b, have been increasing since they were initially produced. Recently, the atmospheric growth rates have been decreasing for the HCFCs (HCFC-22, HCFC-141b and HCFC-142b), increasing for the HFCs (HFC-134a, HFC-125, HFC-23) and stable with little fluctuation for the PFCs (PFC-14 and PFC-116) investigated here. The atmospheric histories (source functions) and natural background mole fractions show that HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125 and HFC-23 have the potential to be oceanic transient tracers for the next few decades only because of the recently imposed bans on production and consumption. When the atmospheric histories of the compounds are not monotonically changing, the equilibrium atmospheric mole fraction (and ultimately the age associated with that mole fraction) calculated from their concentration in the ocean is not unique, reducing their potential as transient tracers. Moreover, HFCs have potential to be oceanic transient tracers for a longer period in the future than HCFCs as the growth rates of HFCs are increasing and those of HCFCs are decreasing in the background atmosphere. PFC-14 and PFC-116, however, have the potential to be tracers for longer periods into the future due to their extremely long lifetimes, steady atmospheric growth rates and no explicit ban on their emissions. In this work, we also derive solubility functions for HCFC-22, HCFC-141b, HCFC-142b, HFC-134a, HFC-125, HFC-23, PFC-14 and PFC-116 in water and seawater to facilitate their use as oceanic transient tracers. These functions are based on the Clark–Glew–Weiss (CGW) water solubility function fit and salting-out coefficients estimated by the poly-parameter linear free-energy relationships (pp-LFERs). Here we also provide three methods of seawater solubility estimation for more compounds. Even though our intention is for application in oceanic research, the work described in this paper is potentially useful for tracer studies in a wide range of natural waters, including freshwater and saline lakes, and, for the more stable compounds, groundwaters.

Biogenic hydrogen sulphide emissions and non-sea sulfate aerosols over the Indian Sundarban mangrove forest - D. Ganguly; R. Ray; N. Majumdar; C. Chowdhury; T. K. Jana (Journal of Atmospheric Chemistry, 2018)

Antidepressant and anxiolytic like effects of Urtica dioica leaves in streptozotocin induced diabetic mice - Sita Sharan Patel; R. S. Ray; Arun Sharma; Vineet Mehta; Anju Katyal; Malairaman Udayabanu (Metabolic Brain Disease, 2018)

Association mapping identifies loci for canopy temperature under drought in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; Antonio R. Asebedo; C. Andy King; E. E. Gbur; Larry C. Purcell (Euphytica, 2018)

Phosphorus Budget of the Sundarban Mangrove Ecosystem: Box Model Approach - R. Ray; N. Majumder; C. Chowdhury; S. Das; T. K. Jana (Estuaries and Coasts, 2018)

Noise Induces Hypothyroidism and Gonadal Dysfunction Via Stimulation of Pineal–Adrenal Axis in Chicks - Prajna Paramita Ray; Tania Chatterjee; Sraboni Roy; Suvojit Rakshit; Madhumita Bhowmik; Jaysree Guha; Aniruddha Maity; Indraneel Saha; Ankur Bhowal; Aniruddha Chatterjee; Supriti Sarkar; Debabrata Nag; et al. (Proceedings of the Zoological Society, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Vitamin D3 attenuates cognitive deficits and neuroinflammatory responses in ICV-STZ induced sporadic Alzheimer’s disease - P. Yamini; R. S. Ray; Kanwaljit Chopra (Inflammopharmacology, 2018)

Erratum: Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

Assessment of village-wise groundwater draft for irrigation: a field-based study in hard-rock aquifers of central India - R. K. Ray; T. H. Syed; Dipankar Saha; B. C. Sarkar; A. K. Patre (Hydrogeology Journal, 2017)

A TaqMan real-time PCR assay for Rhizoctonia cerealis and its use in wheat and soil - J. W. Woodhall; M. J. Brown; K. Perkins; E. Somoza Valdeolmillos; N. Boonham; R. V. Ray (European Journal of Plant Pathology, 2017)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Noble gases fingerprint a metasedimentary fluid source in the Macraes orogenic gold deposit, New Zealand - Nicholas R. J. Goodwin; Ray Burgess; Dave Craw; Damon A. H. Teagle; Chris J. Ballentine (Mineralium Deposita, 2017)
The world-class Macraes orogenic gold deposit (∼10 Moz resource) formed during the late metamorphic uplift of a metasedimentary schist belt in southern New Zealand. Mineralising fluids, metals and metalloids were derived from within the metasedimentary host. Helium and argon extracted from fluid inclusions in sulphide mineral grains (three crush extractions from one sample) have crustal signatures, with no evidence for mantle input (R/Ra = 0.03). Xenon extracted from mineralised quartz samples provides evidence for extensive interaction between fluid and maturing organic material within the metasedimentary host rocks, with 132 Xe/ 36 Ar ratios up to 200 times greater than air. Similarly, I/Cl ratios for fluids extracted from mineralised quartz are similar to those of brines from marine sediments that have interacted with organic matter and are ten times higher than typical magmatic/mantle fluids. The Macraes mineralising fluids were compositionally variable, reflecting either mixing of two different crustal fluids in the metasedimentary pile or a single fluid type that has had varying degrees of interaction with the host metasediments. Evidence for additional input of meteoric water is equivocal, but minor meteoric incursion cannot be discounted. The Macraes deposit formed in a metasedimentary belt without associated coeval magmatism, and therefore represents a purely crustal metamorphogenic end member in a spectrum of orogenic hydrothermal processes that can include magmatic and/or mantle fluid input elsewhere in the world. There is no evidence for involvement of minor intercalated metabasic rocks in the Macraes mineralising system. Hydrothermal fluids that formed other, smaller, orogenic deposits in the same metamorphic belt have less pronounced noble gas and halogen evidence for crustal fluid-rock interaction than at Macraes, but these deposits also formed from broadly similar metamorphogenic processes.

A LC-MS/MS Method for Quantifying Adenosine, Guanosine and Inosine Nucleotides in Human Cells - Leah C. Jimmerson; Lane R. Bushman; Michelle L. Ray; Peter L. Anderson; Jennifer J. Kiser (Pharmaceutical Research, 2017)

Effects of biological, economic and management factors on tuna and billfish stock status - Maite Pons; Trevor A Branch; Michael C Melnychuk; Olaf P Jensen; Jon Brodziak; Jean M Fromentin; Shelton J Harley; Alan C Haynie; Laurie T Kell; Mark N Maunder; Ana M Parma; Victor R Restrepo; et al. (Fish and Fisheries, 2017)
Commercial tunas and billfishes (swordfish, marlins and sailfish) provide considerable catches and income in both developed and developing countries. These stocks vary in status from lightly exploited to rebuilding to severely depleted. Previous studies suggested that this variability could result from differences in life‐history characteristics and economic incentives, but differences in exploitation histories and management measures also have a strong effect on current stock status. Although the status (biomass and fishing mortality rate) of major tuna and billfish stocks is well documented, the effect of these diverse factors on current stock status and the effect of management measures in rebuilding stocks have not been analysed at the global level. Here, we show that, particularly for tunas, stocks were more depleted if they had high commercial value, were long‐lived species, had small pre‐fishing biomass and were subject to intense fishing pressure for a long time. In addition, implementing and enforcing total allowable catches ( TAC s) had the strongest positive influence on rebuilding overfished tuna and billfish stocks. Other control rules such as minimum size regulations or seasonal closures were also important in reducing fishing pressure, but stocks under TAC implementations showed the fastest increase of biomass. Lessons learned from this study can be applied in managing large industrial fisheries around the world. In particular, tuna regional fisheries management organizations should consider the relative effectiveness of management measures observed in this study for rebuilding depleted large pelagic stocks.

Predictive equations for soil shear-wave velocities of Hungarian soils based on MASW and CPT measurements around Győr - O. Kegyes-Brassai; R. P. Ray; P. Tildy (Acta Geodaetica et Geophysica, 2016)

Betrayal: radio-tagged Burmese pythons reveal locations of conspecifics in Everglades National Park - Brian J. Smith; Michael S. Cherkiss; Kristen M. Hart; Michael R. Rochford; Thomas H. Selby; Ray W. Snow; Frank J. Mazzotti (Biological Invasions, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Impact of WWII dumpsites on Saipan (CNMI): heavy metal status of soils and sediments - Gary R. W. Denton; Carmen A. Emborski; April A. B. Hachero; Ray S. Masga; John A. Starmer (Environmental Science and Pollution Research, 2016)

Habitat availability and gene flow influence diverging local population trajectories under scenarios of climate change: a place‐based approach - Donelle Schwalm; Clinton W. Epps; Thomas J. Rodhouse; William B. Monahan; Jessica A. Castillo; Chris Ray; Mackenzie R. Jeffress (Global Change Biology, 2016)
Ecological niche theory holds that species distributions are shaped by a large and complex suite of interacting factors. Species distribution models ( SDM s) are increasingly used to describe species’ niches and predict the effects of future environmental change, including climate change. Currently, SDM s often fail to capture the complexity of species’ niches, resulting in predictions that are generally limited to climate‐occupancy interactions. Here, we explore the potential impact of climate change on the American pika using a replicated place‐based approach that incorporates climate, gene flow, habitat configuration, and microhabitat complexity into SDM s. Using contemporary presence–absence data from occupancy surveys, genetic data to infer connectivity between habitat patches, and 21 environmental niche variables, we built separate SDM s for pika populations inhabiting eight US National Park Service units representing the habitat and climatic breadth of the species across the western United States. We then predicted occurrence probability under current (1981–2010) and three future time periods (out to 2100). Occurrence probabilities and the relative importance of predictor variables varied widely among study areas, revealing important local‐scale differences in the realized niche of the American pika. This variation resulted in diverse and – in some cases – highly divergent future potential occupancy patterns for pikas, ranging from complete extirpation in some study areas to stable occupancy patterns in others. Habitat composition and connectivity, which are rarely incorporated in SDM projections, were influential in predicting pika occupancy in all study areas and frequently outranked climate variables. Our findings illustrate the importance of a place‐based approach to species distribution modeling that includes fine‐scale factors when assessing current and future climate impacts on species’ distributions, especially when predictions are intended to manage and conserve species of concern within individual protected areas.

A Novel Delivery System for the Root Symbiotic Fungus, Sebacina vermifera, and Consequent Biomass Enhancement of Low Lignin COMT Switchgrass Lines - Prasun Ray; Takako Ishiga; Stephen R. Decker; Geoffrey B. Turner; Kelly D. Craven (BioEnergy Research, 2015)

Equivalent Isopropanol Concentrations of Aromatic Amino Acids Interactions with Lipid Vesicles - Merrell A. Johnson; Bruce D. Ray; Stephen R. Wassall; Horia I. Petrache (The Journal of Membrane Biology, 2015)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Life at the leading edge: genetic impoverishment of the spotted bass, Micropterus punctulatus, at its Western edge - J. W. Ray; M. Husemann; D. J. Lutz-Carrillo; R. S. King; P. D. Danley (Environmental Biology of Fishes, 2015)

Tuberculosis surveillance of elephants (Elephas maximus) in Nepal at the captive-wild interface - Susan K. Mikota; Kamal Gairhe; Kamal Giri; Karin Hamilton; Michele Miller; Sarad Paudel; Konstantin Lyashchenko; R. Scott Larsen; Janet B. Payeur; W. Ray Waters; Rena Greenwald; Genevieve Dumonceaux; et al. (European Journal of Wildlife Research, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Methane and nitrous oxide emissions from rice and maize production in diversified rice cropping systems - Sebastian Weller; David Kraus; Kevin Ray P. Ayag; Reiner Wassmann; M. C. R. Alberto; Klaus Butterbach-Bahl; Ralf Kiese (Nutrient Cycling in Agroecosystems, 2015)

Uromycladium falcatarium sp. nov., the cause of gall rust on Paraserianthes falcataria in south-east Asia - Chanintorn Doungsa-ard; Alistair R. McTaggart; Andrew D. W. Geering; Teresita U. Dalisay; Jane Ray; Roger G. Shivas (Australasian Plant Pathology, 2015)

Short-term escitalopram treatment and hippocampal volume - Beata R. Godlewska; Helge W. W. Hasselmann; Artemis Igoumenou; Ray Norbury; Philip J. Cowen (Psychopharmacology, 2014)

Identification of a single gene for seed coat impermeability in soybean PI 594619 - Hirut Kebede; James R. Smith; Jeffery D. Ray (Theoretical and Applied Genetics, 2014)

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Molecular determinants of odorant receptor function in insects - Anandasankar Ray; Wynand van der Goes van Naters; John R Carlson (Journal of Biosciences, 2014)

Quantitative Study of As (V) and As (III) Interaction with Mangrove DNA by Molecular Fluorescence Spectroscopy - N. Majumder; C. Chowdhury; R. Ray; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2014)

Predictors of smoking lapse in a human laboratory paradigm - Daniel J. O. Roche; Spencer Bujarski; Nathasha R. Moallem; Iris Guzman; Jenessa R. Shapiro; Lara A. Ray (Psychopharmacology, 2014)

Trading in snails: plant nurseries as transport hubs for non-native species - Elizabeth A. Bergey; Laura L. Figueroa; Charles M. Mather; Rebekah J. Martin; Eric J. Ray; Jobin T. Kurien; David R. Westrop; Phushewan Suriyawong (Biological Invasions, 2014)

Secondary cell wall composition and candidate gene expression in developing willow (Salix purpurea) stems - Yongfang Wan; Cristina Gritsch; Theodora Tryfona; Mike J. Ray; Ambrose Andongabo; Keywan Hassani-Pak; Huw D. Jones; Paul Dupree; Angela Karp; Peter R. Shewry; Rowan A. C. Mitchell (Planta, 2014)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

The mechanism by which MEK/ERK regulates JNK and p38 activity in polyamine depleted IEC-6 cells during apoptosis - Mitul N. Bavaria; Shi Jin; Ramesh M. Ray; Leonard R. Johnson (Apoptosis, 2014)

Cyclin-dependent kinases regulate apoptosis of intestinal epithelial cells - Sujoy Bhattacharya; Ramesh M. Ray; Leonard R. Johnson (Apoptosis, 2014)

gltB/D Mutants of Xanthomonas oryzae pv. oryzae are Virulence Deficient - Alok Pandey; Suvendra Kumar Ray; Ramesh V. Sonti; R. Rajeshwari (Current Microbiology, 2014)

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Age and geochemistry of the Newania dolomite carbonatites, India: implications for the source of primary carbonatite magma - Jyotiranjan S. Ray; Kanchan Pande; Rajneesh Bhutani; Anil D. Shukla; Vinai K. Rai; Alok Kumar; Neeraj Awasthi; R. S. Smitha; Dipak K. Panda (Contributions to Mineralogy and Petrology, 2013)

TMEM43 mutations associated with arrhythmogenic right ventricular cardiomyopathy in non-Newfoundland populations - Berivan Baskin; Jon R. Skinner; Shubhayan Sanatani; Deborah Terespolsky; Andrew D. Krahn; Peter N. Ray; Stephen W. Scherer; Robert M. Hamilton (Human Genetics, 2013)

Sub-daily alias and draconitic errors in the IGS orbits - J. Griffiths; Jim R. Ray (GPS Solutions, 2013)

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Implication of Organic Matter on Arsenic and Antimony Sequestration in Sediment: Evidence from Sundarban Mangrove Forest, India - S. K. Mandal; R. Ray; C. Chowdhury; N. Majumder; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2013)

Genome size variation among sex types in dioecious and trioecious Caricaceae species - Andrea R. Gschwend; Ching Man Wai; Francis Zee; Aru K. Arumuganathan; Ray Ming (Euphytica, 2013)

A new gene that controls seed coat wrinkling in soybean - Hirut Kebede; James R. Smith; Jeffery D. Ray (Euphytica, 2013)

Calibration of Ocean Wave Measurements by the TOPEX, Jason-1 , and Jason-2 Satellites - R. D. Ray; B. D. Beckley (Marine Geodesy, 2012)

Mitigating future climate change effects by shifting planting dates of crops in rice–wheat cropping system - S. K. Jalota; Harsimran Kaur; S. S. Ray; R. Tripathi; Bharat Bhushan Vashisht; S. K. Bal (Regional Environmental Change, 2012)

IGS08: the IGS realization of ITRF2008 - P. Rebischung; J. Griffiths; J. Ray; R. Schmid; X. Collilieux; B. Garayt (GPS Solutions, 2012)

Unsupervised and supervised classification of hyperspectral imaging data using projection pursuit and Markov random field segmentation - A. Sarkar; A. Vulimiri; S. Paul; Jawaid Iqbal; A. Banerjee; R. Chatterjee; S. S. Ray (International Journal of Remote Sensing, 2012)

Phosphorus Solubilization by Thermotolerant Bacillus subtilis Isolated from Cow Dung Microflora - Manas R. Swain; K. Laxminarayana; Ramesh C. Ray (Agricultural Research, 2012)

B MEY as a fisheries management target - Quentin R Grafton; Tom Kompas; Tuong N Che; Long Chu; Ray Hilborn (Fish and Fisheries, 2012)
This paper evaluates the implications of managing fisheries to achieve a B MEY target, or a biomass level that maximizes net economic returns in the fishery, and discusses the role of private ownership and the trade‐offs between economic and conservation benefits in this setting. The paper shows how a B MEY target can be used to: (i) determine relative employment and profitability measures; (ii) account for both the harvesting and processing sectors; and (iii) incorporate the interests of consumers and producers of fish. The profits–employment trade‐off of adopting a B MEY target vs. a traditional B MSY target is calculated using a model and data from the Western and Central Pacific tuna fisheries (WCPTF), while a generic bioeconomic model is constructed to show numerical values of B MEY from including processing and/or retail sectors and the consumer benefits of harvesting fish. For the WCPTF, results show that the long‐term gains per job lost from pursuing a B MEY target are worth several times the value of the average GDP per capita of Pacific Island Countries. The generic bioeconomic model shows that including a processing and/or retail sector, as well as measures of consumer benefit, lowers the B MEY target. However, there remains a broad range of parameter values for which B MEY is still greater than biomass at maximum sustainable yield, or B MSY . The paper also illustrates cases where B MEY > B MSY at different values of the price elasticity of demand, margins for processing and/or retail sectors and values of the discount rate.

Identification of a new soybean rust resistance gene in PI 567102B - Shuxian Li; James R. Smith; Jeffery D. Ray; Reid D. Frederick (Theoretical and Applied Genetics, 2012)

Effects of roof and rainwater characteristics on copper concentrations in roof runoff - Gretchen K. Bielmyer; W. Ray Arnold; Joseph R. Tomasso; Jeff J. Isely; Stephen J. Klaine (Environmental Monitoring and Assessment, 2012)

Particle Size Distribution of Ambient Aerosols in an Industrial Area - B. Padma Rao; A. Srivastava; F. Yasmin; S. Ray; N. Gupta; C. Chauhan; C. V. C. Rao; S. R. Wate (Bulletin of Environmental Contamination and Toxicology, 2012)

Isolation and characterization of polymorphic microsatellite loci from the invasive plant Lantana camara L. - Avik Ray; R. C. Sumangala; G. Ravikanth; R. Uma Shaanker; Suhel Quader (Conservation Genetics Resources, 2012)

Rice Blast Management Through Host-Plant Resistance: Retrospect and Prospects - T. R. Sharma; A. K. Rai; S. K. Gupta; J. Vijayan; B. N. Devanna; S. Ray (Agricultural Research, 2012)

Soluplus-Solubilized Citrated Camptothecin—A Potential Drug Delivery Strategy in Colon Cancer - Naveen K. Thakral; Alok R. Ray; Daniel Bar-Shalom; André Huss Eriksson; Dipak K. Majumdar (AAPS PharmSciTech, 2012)

Genomic Location of a Gene Conditioning a Miniature Phenotype in Soybean [Glycine max (L.) Merr.] - Jeffery D. Ray; James R. Smith; Earl Taliercio; Felix B. Fritschi (Journal of Plant Biology, 2012)

The sex-specific region of sex chromosomes in animals and plants - Andrea R. Gschwend; Laura A. Weingartner; Richard C. Moore; Ray Ming (Chromosome Research, 2012)

Validation of Concussion Risk Curves for Collegiate Football Players Derived from HITS Data - James R. Funk; Steven Rowson; Ray W. Daniel; Stefan M. Duma (Annals of Biomedical Engineering, 2012)

Discrimination of Spectrally-Close Crops Using Ground-Based Hyperspectral Data - K. R. Manjunath; Shibendu Shankar Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2011)

Lifelong stable human insulin expression in transgenic tilapia expressing a humanized tilapia insulin gene - Olga Hrytsenko; Gina R. Rayat; Bao-You Xu; Richard Krause; Bill Pohajdak; Ray V. Rajotte; James R. Wright (Transgenic Research, 2011)

Introduction to Special Issue of Bulletin of Volcanology on “Advances in Kimberlite Geology and Volcanology” - Ray Cas; J. K. Russell; R. Stephen J. Sparks (Bulletin of Volcanology, 2011)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Delayed reward discounting and addictive behavior: a meta-analysis - James MacKillop; Michael T. Amlung; Lauren R. Few; Lara A. Ray; Lawrence H. Sweet; Marcus R. Munafò (Psychopharmacology, 2011)

Utility of Hyperspectral Data for Potato Late Blight Disease Detection - Shibendu Shankar Ray; Namrata Jain; R. K. Arora; S. Chavan; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2011)

Effects of air pollution on the respiratory health of children: a study in the capital city of India - Shabana Siddique; Manas R. Ray; Twisha Lahiri (Air Quality, Atmosphere & Health, 2011)

Cold-induced mortality of invasive Burmese pythons in south Florida - Frank J. Mazzotti; Michael S. Cherkiss; Kristen M. Hart; Ray W. Snow; Michael R. Rochford; Michael E. Dorcas; Robert N. Reed (Biological Invasions, 2011)

Mdm2 inhibition induces apoptosis in p53 deficient human colon cancer cells by activating p73- and E2F1-mediated expression of PUMA and Siva-1 - Ramesh M. Ray; Sujoy Bhattacharya; Leonard R. Johnson (Apoptosis, 2011)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

Upwelling linked to warm summers and bleaching on the Great Barrier Reef - Ray Berkelmans; Scarla J. Weeks; Craig R. Steinberga (Limnology and Oceanography, 2010)
We investigate a range of indices to quantify upwelling on the central Great Barrier Reef (GBR), Australia, so that environmental and biological relationships associated with upwelling in this area can be explored. We show that "Upwelling days" (the number of days of upwelling) and diurnal variation in subsurface temperature (maximum‐minimum, 20‐m depth) are satisfactory metrics to describe the duration and intensity of upwelling events, respectively. We use these to examine key characteristics of shelf‐break upwelling in the central GBR. Our results show, somewhat paradoxically, that although upwelling involves cold water being brought near to the surface, it is linked to positive thermal anomalies on the GBR, both locally and regionally. Summers (December to February) with strongest upwelling occurred during the GBR‐wide bleaching events of 1997‐1998 and 2001‐2002. Upwelling in the GBR is enhanced during doldrums conditions that were a feature of these summers. During these conditions, the poleward‐flowing East Australian Current flows faster, lifting the thermocline closer to the surface, spilling more sub‐thermocline waters onto the shelf. Doldrums conditions also result in intense local heating, stratification of the water column, and, when severe, coral bleaching. Upwelling intrusions are spatially restricted (central GBR), generally remain subsurface, and are often intermittent, allowing GBR‐wide bleaching to occur despite conditions resulting in enhanced upwelling. Intense upwelling events precede anomalous seasonal temperature maxima by up to 2 months and bleaching by 1‐3 wk, leading to the prospect of using upwelling activity as a seasonal forecasting index of unusually warm summers and widespread bleaching.

Level of Heavy Metals in Some Edible Marine Fishes of Mangrove Dominated Tropical Estuarine Areas of Hooghly River, North East Coast of Bay of Bengal, India - T. K. De; M. De; S. Das; R. Ray; P. B. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2010)

Assessment of the Jason-2 Extension to the TOPEX/Poseidon, Jason-1 Sea-Surface Height Time Series for Global Mean Sea Level Monitoring - B. D. Beckley; N. P. Zelensky; S. A. Holmes; F. G. Lemoine; R. D. Ray; G. T. Mitchum; S. D. Desai; S. T. Brown (Marine Geodesy, 2010)

Thymoquinone-induced Neu4 sialidase activates NFκB in macrophage cells and pro-inflammatory cytokines in vivo - Trisha M. Finlay; Samar Abdulkhalek; Alanna Gilmour; Christina Guzzo; Preethi Jayanth; Schammim Ray Amith; Katrina Gee; Rudi Beyaert; Myron R. Szewczuk (Glycoconjugate Journal, 2010)

Penetration of cover crop roots through compacted soils - Guihua Chen; Ray R. Weil (Plant and Soil, 2010)

Thymoquinone from nutraceutical black cumin oil activates Neu4 sialidase in live macrophage, dendritic, and normal and type I sialidosis human fibroblast cells via GPCR Gαi proteins and matrix metalloproteinase-9 - Trisha M. Finlay; Preethi Jayanth; Schammim Ray Amith; Alanna Gilmour; Christina Guzzo; Katrina Gee; Rudi Beyaert; Myron R. Szewczuk (Glycoconjugate Journal, 2010)

Forage radish and cereal rye cover crop effects on mycorrhizal fungus colonization of maize roots - Charles M. White; Ray R. Weil (Plant and Soil, 2010)

Respiratory muscle training reduces the work of breathing at depth - Andrew D. Ray; David R. Pendergast; Claes E. G. Lundgren (European Journal of Applied Physiology, 2010)

High-Oil Soybean for More Efficient Energy Conversion to Soy-Based Biodiesel - Robert L. Paris; Jeffery D. Ray; James R. Smith; Debbie L. Boykin (Natural Resources Research, 2009)

Dependence of pathogen molecule-induced Toll-like receptor activation and cell function on Neu1 sialidase - Schammim Ray Amith; Preethi Jayanth; Susan Franchuk; Sarah Siddiqui; Volkan Seyrantepe; Katrina Gee; Sameh Basta; Rudi Beyaert; Alexey V. Pshezhetsky; Myron R. Szewczuk (Glycoconjugate Journal, 2009)

Volcanology and eruptive styles of Barren Island: an active mafic stratovolcano in the Andaman Sea, NE Indian Ocean - Hetu C. Sheth; Jyotiranjan S. Ray; Rajneesh Bhutani; Alok Kumar; R. S. Smitha (Bulletin of Volcanology, 2009)

Hippuric acid and benzoic acid inhibition of urine derived N 2 O emissions from soil - JANET E. BERTRAM; TIM J. CLOUGH; ROBERT R. SHERLOCK; LEO M. CONDRON; MAUREEN O'CALLAGHAN; NAOMI S. WELLS; JESSICA L. RAY (Global Change Biology, 2009)
Atmospheric concentrations of the greenhouse gas nitrous oxide (N 2 O) have continued to rise since the advent of the industrial era, largely because of the increase in agricultural land use. The urine deposited by grazing ruminant animals is a major global source of agricultural N 2 O. With the first commitment period for reducing greenhouse gas emissions under the Kyoto Protocol now underway, mitigation options for ruminant urine N 2 O emissions are urgently needed. Recent studies showed that increasing the urinary concentration of the minor urine constituent hippuric acid resulted in reduced emissions of N 2 O from a sandy soil treated with synthetic bovine urine, due to a reduction in denitrification. A similar effect was seen when benzoic acid, a product of hippuric acid hydrolysis, was used. This current laboratory experiment aimed to investigate these effects using real cow urine for the first time. Increased concentrations of hippuric acid or benzoic acid in the urine led to reduction of N 2 O emissions by 65% (from 17% to 2 O fluxes. This study indicates the potential for developing a novel mitigation strategy based on manipulation of urine composition through ruminant diet.

Genetics and mapping of adult plant rust resistance in soybean PI 587886 and PI 587880A - Jeffery D. Ray; Wilfrido Morel; James R. Smith; Reid D. Frederick; Monte R. Miles (Theoretical and Applied Genetics, 2009)

Application of manure to no-till soils: phosphorus losses by sub-surface and surface pathways - Peter J. A. Kleinman; Andrew N. Sharpley; Lou S. Saporito; Anthony R. Buda; Ray B. Bryant (Nutrient Cycling in Agroecosystems, 2009)

On the precision and accuracy of IGS orbits - Jake Griffiths; Jim R. Ray (Journal of Geodesy, 2009)

Fruit Development, Ripening and Quality Related Genes in the Papaya Genome - Robert E. Paull; Beth Irikura; Pingfang Wu; Helen Turano; Nancy Jung Chen; Andrea Blas; John K. Fellman; Andrea R. Gschwend; Ching Man Wai; Qingyi Yu; Gernot Presting; Maqsudul Alam; et al. (Tropical Plant Biology, 2008)

Comparison of Cytochrome P450 Genes from Six Plant Genomes - David R. Nelson; Ray Ming; Maqsudul Alam; Mary A. Schuler (Tropical Plant Biology, 2008)

Soil fertility increases with plant species diversity in a long-term biodiversity experiment - Ray Dybzinski; Joseph E. Fargione; Donald R. Zak; Dario Fornara; David Tilman (Oecologia, 2008)

Biocontrol Efficacy of Bacillus subtilis Strains Isolated from Cow Dung Against Postharvest Yam (Dioscorea rotundata L.) Pathogens - M. R. Swain; R. C. Ray; C. S. Nautiyal (Current Microbiology, 2008)

Trace Element Concentrations in Blood of Nesting King Eiders in the Canadian Arctic - Mark Wayland; Ray T. Alisauskas; Dana K. Kellett; Katherine R. Mehl (Archives of Environmental Contamination and Toxicology, 2008)

Evaluation of EO-1 hyperion data for agricultural applications - Anshu Miglani; S. S. Ray; R. Pandey; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2008)

Characterization of periodic variations in the GPS satellite clocks - Kenneth L. Senior; Jim R. Ray; Ronald L. Beard (GPS Solutions, 2008)

Effect of timing of fungicide application on the development of Fusarium head blight and the accumulation of deoxynivalenol (DON) in winter wheat grain - S. Pirgozliev; R. Ray; S. Edwards; M. Hare; P. Jenkinson (Cereal Research Communications, 2008)

High radiogenic heat production in the Kerala Khondalite Block, Southern Granulite Province, India - Labani Ray; Sukanta Roy; R. Srinivasan (International Journal of Earth Sciences, 2008)

Heat flow and crustal thermal structure in the Late Archaean Closepet Granite batholith, south India - Sukanta Roy; Labani Ray; Anurup Bhattacharya; R. Srinivasan (International Journal of Earth Sciences, 2008)

Characterization of the complete genome of influenza A (H5N1) virus isolated during the 2006 outbreak in poultry in India - Koninika Ray; Varsha A. Potdar; Sarah S. Cherian; Shailesh D. Pawar; Santosh M. Jadhav; Shamal R. Waregaonkar; Anshu A. Joshi; Akhilesh C. Mishra (Virus Genes, 2008)

Pharmacodynamic and pharmacokinetic characterisation of RBx 7796: a novel 5-lipoxygenase inhibitor - R. K. Shirumalla; P. Sharma; S. G. Dastidar; J. K. Paliwal; S. Kakar; B. Varshney; G. Singh Saini; V. Sattigeri; M. Salman; A. Ray (Inflammation Research, 2008)

Colonization history of the Swiss Rhine basin by the bullhead ( Cottus gobio ): inference under a Bayesian spatially explicit framework - SAMUEL NEUENSCHWANDER; CARLO R. LARGIADÈR; NICOLAS RAY; MATHIAS CURRAT; PASCAL VONLANTHEN; LAURENT EXCOFFIER (Molecular Ecology, 2008)
The present distribution of freshwater fish in the Alpine region has been strongly affected by colonization events occurring after the last glacial maximum (LGM), some 20 000 years ago. We use here a spatially explicit simulation framework to model and better understand their colonization dynamics in the Swiss Rhine basin. This approach is applied to the European bullhead ( Cottus gobio ), which is an ideal model organism to study fish past demographic processes since it has not been managed by humans. The molecular diversity of eight sampled populations is simulated and compared to observed data at six microsatellite loci under an approximate Bayesian computation framework to estimate the parameters of the colonization process. Our demographic estimates fit well with current knowledge about the biology of this species, but they suggest that the Swiss Rhine basin was colonized very recently, after the Younger Dryas some 6600 years ago. We discuss the implication of this result, as well as the strengths and limits of the spatially explicit approach coupled to the approximate Bayesian computation framework.

History repeated: recent and historical mitochondrial introgression between the current darter Etheostoma uniporum and rainbow darter Etheostoma caeruleum (Teleostei: Percidae) - J. M. Ray; N. J. Lang; R. M. Wood; R. L. Mayden (Journal of Fish Biology, 2008)
Incongruence between recognized taxonomy and phylogenetic relationships between two species from a diverse clade (Percidae: Etheostomatinae) of stream fishes was found in a mitochondrial (mt) DNA gene tree. Two darters in subgenus Oligocephalus , Etheostoma uniporum current darter and Etheostoma caeruleum rainbow darter were sampled throughout their sympatric distribution in the Ozark Highlands of the central United States. Sequences from cytochrome (cyt) b and the first intron of the nuclear marker S7 were analysed separately using maximum parsimony and Bayesian methods. Cyt b recovered both species as polyphyletic; E. uniporum haplotypes were interspersed within E. caeruleum . However, both species were monophyletic and non‐sister taxa based on S7. The cyt b gene tree pattern is caused by introgressive hybridization resulting in the mtDNA replacement of E. uniporum haplotypes by those of E. caeruleum . Some E. uniporum haplotypes are shared with geographically proximate E. caeruleum , and this is consistent with recent hybridization, while other E. uniporum haplotypes indicate historical sorting of introgressed lineages. The mechanism of introgression is likely asymmetric sneaking behaviour by male E. uniporum , a mating tactic observed in related species. MtDNA replacement may have occurred in E. uniporum due to drift fixation in a historically small female effective population. Additional evidence for darter hybridization will likely be discovered in future molecular genetic surveys of the nearly 200 species in eastern North America.

Formation and characterization of three dimensional human hepatocyte cell line spheroids on chitosan matrix for in vitro tissue engineering applications - Poonam Verma; Vipin Verma; Pratima Ray; Alok R. Ray (In Vitro Cellular & Developmental Biology - Animal, 2007)

In Vitro Characterization of a Compliant Biodegradable Scaffold with a Novel Bioreactor System - Antonio R. Webb; Bryan D. Macrie; Ananda S. Ray; Jack E. Russo; Andrew M. Siegel; Matthew R. Glucksberg; Guillermo A. Ameer (Annals of Biomedical Engineering, 2007)

Nocardiosis in a tertiary care hospital in North India and review of patients reported from India - M. R. Shivaprakash; Pooja Rao; Jharna Mandal; Manisha Biswal; Sunita Gupta; Pallab Ray; Arunaloke Chakrabarti (Mycopathologia, 2007)

Fuzzy-based method for landslide hazard assessment in active seismic zone of Himalaya - P. K. Champati ray; Suvarna Dimri; R. C. Lakhera; Santosh Sati (Landslides, 2007)

Tidal analysis experiments with sun-synchronous satellite altimeter data - R. D. Ray (Journal of Geodesy, 2007)

The role of medial prefrontal cortex in context-specific inhibition during reversal learning of a visual discrimination - R. J. McDonald; N. Foong; C. Ray; Z. Rizos; N. S. Hong (Experimental Brain Research, 2007)

RBx 7796: A novel inhibitor of 5-lipoxygenase - R. K. Shirumalla; K. S. Naruganahalli; S. G. Dastidar; V. Sattigeri; G. Kaur; C. Deb; J. B. Gupta; M. Salman; A. Ray (Inflammation Research, 2006)

Induced abortions and the risk of all cancers combined and site-specific cancers in Shanghai - Karin A. Rosenblatt; Dao L. Gao; Roberta M. Ray; Michelle R. Rowland; Zakia C. Nelson; Karen J. Wernli; Wenjin Li; David B. Thomas (Cancer Causes & Control, 2006)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Analysis of papaya BAC end sequences reveals first insights into the organization of a fruit tree genome - Chun Wan J. Lai; Qingyi Yu; Shaobin Hou; Rachel L. Skelton; Meghan R. Jones; Kanako L. T. Lewis; Jan Murray; Moriah Eustice; Peizhu Guan; Ricelle Agbayani; Paul H. Moore; Ray Ming; et al. (Molecular Genetics and Genomics, 2006)

Gape Limitation, Prey Size Refuges and the Top–down Impacts of Piscivorous Largemouth Bass in Shallow Pond Ecosystems - Weston H. Nowlin; Ray W. Drenner; Kirk R. Guckenberger; Mark A. Lauden; G. Todd Alonso; Joseph E. Fennell; Judson L. Smith (Hydrobiologia, 2006)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Effect of ascorbic acid on prevention of hypercholesterolemia induced atherosclerosis - S. Das; R. Ray; Snehlata; N. Das; L. M. Srivastava (Molecular and Cellular Biochemistry, 2006)

Influence of menstrual cycle phase on pulmonary function in asthmatic athletes - Kristin I. Stanford; Timothy D. Mickleborough; Shahla Ray; Martin R. Lindley; David M. Koceja; Joel M. Stager (European Journal of Applied Physiology, 2006)

Reproductive history, occupational exposures, and thyroid cancer risk among women textile workers in Shanghai, China - E. Y. Wong; R. Ray; D. L. Gao; K. J. Wernli; W. Li; E. D. Fitzgibbons; Z. Feng; D. B. Thomas; H. Checkoway (International Archives of Occupational and Environmental Health, 2006)

Letter to the Editor - Basant K. Tiwary; R. Kirubagaran; Arun K. Ray (Reviews in Fish Biology and Fisheries, 2006)

A Quick appraisal of ground deformation in indian region due to the october 8, 2005 earthquake, Muzaffarabad, Pakistan - P. K. Champati ray; R. J. G. Perumal; V. C. Thakur; M. I. Bhat; M. A. Mallik; Vivek Kumar Singh; R. C. Lakhera (Journal of the Indian Society of Remote Sensing, 2005)

The cystic fibrosis transmembrane conductance regulator gene and ion channel function in patients with idiopathic pancreatitis - Michele D. Bishop; Steven D. Freedman; Julian Zielenski; Najma Ahmed; Annie Dupuis; Sheelagh Martin; Lynda Ellis; Julie Shea; Isobel Hopper; Mary Corey; Paul Kortan; Gregory Haber; et al. (Human Genetics, 2005)

Colorectal Cancer Incidence Among Female Textile Workers in Shanghai, China: A Case-cohort Analysis of Occupational Exposures - A.J. De Roos; R. M. Ray; D. L. Gao; K. J. Wernli; E. D. Fitzgibbons; F. Ziding; G. Astrakianakis; D. B. Thomas; H. Checkoway (Cancer Causes & Control, 2005)

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

Decreased apoptosis in polyamine depleted IEC-6 cells depends on Akt-mediated NF-κB activation but not GSK3β activity - S. Bhattacharya; R. M. Ray; L. R. Johnson (Apoptosis, 2005)

The biology of triploid fish - Basant K. Tiwary; R. Kirubagaran; Arun K. Ray (Reviews in Fish Biology and Fisheries, 2004)

Low Levels of Nucleotide Diversity in Crocodylus moreletii and Evidence of Hybridization with C. acutus - David A. Ray; Jennifer A. Dever; Steven G. Platt; Thomas R. Rainwater; Adam G. Finger; Scott T. McMurry; Mark A. Batzer; Brady Barr; Peter J. Stafford; Jenna McKnight; Llewellyn D. Densmore (Conservation Genetics, 2004)

Releasing the peri-neuronal net to patch-clamp neurons in adult CNS - Fernando R. Fernandez; Suzanne Sinclair; Michael L. Molineux; W. Hamish Mehaffey; Ray W. Turner; Ezequiel Morales (Pflügers Archiv - European Journal of Physiology, 2004)

Controls of fluid chemistry and complexation on rare-earth element contents of anhydrite from the Pacmanus subseafloor hydrothermal system, Manus Basin, Papua New Guinea - Wolfgang Bach; Stephen Roberts; David A. Vanko; Ray A. Binns; Chris J. Yeats; Paul R. Craddock; Susan E. Humphris (Mineralium Deposita, 2003)

Loss of purinergic P2X receptor innervation in human detrusor and subepithelium from adults with sensory urgency - Fiona R. Ray; Kate H. Moore; Mitchell A. Hansen; Julian A. Barden (Cell and Tissue Research, 2003)

Spatial and Temporal Disturbance Characteristics of Oak-Dominated Old-Growth Stands in the Central Hardwood Forest Region - James S. Rentch; Mary Ann Fajvan; Ray R. Hicks (Forest Science, 2003)
Using a radial growth averaging technique, decadal-scale growth changes of 150- to 350-yr-old overstory oaks were used to identify canopy disturbance events in five old-growth stands, and canopy disturbance intervals were estimated using frequency analysis. Stem maps and tree-establishment and canopy-accession chronologies were then used to reconstruct the size of canopy openings. Between 1700 and 1990, median canopy disturbance interval was approximately 3 yr for each stand; larger disturbances involving two or more trees occurred about every 16 yr per stand. Based on age distribution of the oldest cohorts, three stands became established after a major disturbance, but the majority of multiple-tree disturbances were associated with gaps < 200 m2 in area. Historic disturbance frequency and size distribution of canopy gaps suggest that the oak components of these stands persisted by utilizing a variety of growth strategies appropriate to large and small openings. The absence of significant changes in overstory disturbance frequencies further suggests that increases in the level of understory competition are responsible for the present-day decline in oak dominance.

Carbon, Carbon, Everywhere, nor Any Drop to … Market - Robert R. Dorsch; Ray W. Miller (Journal of Industrial Ecology, 2003)

Type I Burst Excitability - Carlo R. Laing; Brent Doiron; André Longtin; Liza Noonan; Ray W. Turner; Leonard Maler (Journal of Computational Neuroscience, 2003)

DDT and HCH Residues in Basmati Rice (Oryza sativa) Cultivated in Dehradun (India) - G. Suresh Babu; M. Farooq; R. S. Ray; P. C. Joshi; P. N. Viswanathan; R. K. Hans (Water, Air, & Soil Pollution, 2003)

Productivity optimisation in weak sedimentary formations for improved coal production and roof stability—an approach - V. M. S. R. Murthy; Santosh Kumar Ray (Geotechnical and Geological Engineering, 2002)

Cloning and transcriptional analysis of the Thermoanaerobacter ethanolicus strain 39E maltose ABC transport system - Chris R. Jones; Myrna Ray; Herbert J. Strobel (Extremophiles, 2002)

Short-arc analysis of intersatellite tracking data in a gravity mapping mission - D. D. Rowlands; R. D. Ray; D. S. Chinn; F. G. Lemoine (Journal of Geodesy, 2002)

Transcriptional Analysis of the Xylose ABC Transport Operons in the Thermophilic Anaerobe Thermoanaerobacter ethanolicus - Chris R. Jones; Myrna Ray; Herbert J. Strobel (Current Microbiology, 2002)

Using GIS for siting artificial reefs—Data issues, problems and solutions: ‘Real World’ to ‘Real World’ - D. R. Green; S. T. Ray (Journal of Coastal Conservation, 2002)

The effect of vapor pressure deficit on maize transpiration response to a drying soil - Jeffery D. Ray; Russ W. Gesch; Thomas R. Sinclair; L. Hartwell Allen (Plant and Soil, 2002)

Short photoperiod inhibits winter growth of subtropical grasses - Thomas R. Sinclair; Paul Mislevy; Jeffery D. Ray (Planta, 2001)

Temperature Sensitivity of Timing Measurements Using Dorne Margolin Antennas - J. R. Ray; K. Senior (GPS Solutions, 2001)

Phylogenetic Placement of a Novel Tenuivirus from the Grass Urochloa plantaginea - Joachim R. de Miranda; Miguel Muñoz; Ray Wu; Ana M. Espinoza (Virus Genes, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Plasma levels of Gonadotropin-II and gonadal sex steroids in triploid catfish, Heteropneustes fossilis (Bloch) - Basant K. Tiwary; R. Kirubagaran; Arun K. Ray (Fish Physiology and Biochemistry, 2001)

Serum lipids, lipoproteins and sex-hormone binding globulin in breast cancer - A. Ray; S. L. Dayalu Naik; A. K. Bahadur; S. T. Pasha; R. S. Rautela; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Status of epidermal growth factor receptors family in hormone-dependent carcinomas of the breast and prostate with reference to serum lipids and lipoproteins - D. Jain; A. Ray; A. K. Bahadur; K. U. Chaturvedi; R. Sood; S. Sharma; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Recent Improvements to IERS Bulletin A Combination and Prediction - Brian J. Luzum; Jim R. Ray; Merri S. Carter; F. Jerry Josties (GPS Solutions, 2001)

Influence of Timber Extraction Routes on Central African Small‐Mammal Communities, Forest Structure, and Tree Diversity - Jay R. Malcolm; Justina C. Ray (Conservation Biology, 2000)
Despite increasing pressure to harvest timber from African tropical forests, the short‐ and long‐term ecological effects of qualitative and quantitative variation in extraction practices rarely have been examined. At a site in the southwestern Central African Republic, we surveyed rodent and tree communities and vegetation structure in unlogged forest and along skid trails and secondary and primary access roads at 12 and 19 years after logging. The most important source of variation among transects was the type of logging road: primary and secondary access roads showed the greatest change and skid trails the least. An intercorrelated suite of changes occurred along the margins of the roads, including changes in rodent community composition, increases in rodent abundance and diversity, changes in the height distribution of rodent abundance, increases in understory foliage density, and decreases in sapling density and tree species richness. Ecological changes along the secondary roads were nearly as strong as those along primary roads, despite the fact that secondary roads had been abandoned immediately after logging, whereas primary roads had been traveled up to the time of the research. Continuing edge‐induced effects along graded road margins at between 12 and 19 years after logging were indicated by differences in tree species composition, sapling and tree densities, and understory density. Our results support conclusions of increased disturbance to rainforest communities with increasingly destructive road construction techniques and suggest that canopy damage rather than stem damage is the most appropriate measure of logging damage. Although minimizing the length of access roads is important in reducing ecological effects, it should not be achieved at the expense of increased canopy damage. Rodent communities appear to be an easily measured indicator of these ecological changes and may be responsive to landscape‐level changes in forest cover and degradation.

Influence of Timber Extraction Routes on Central African Small-Mammal Communities, Forest Structure, and Tree Diversity - Jay R. Malcolm; Justina C. Ray (Conservation Biology, 2000)

Gonadal development in triploid Heteropneustes fossilis - B. K. Tiwary; R. Kirubagaran; A. K. Ray (Journal of Fish Biology, 2000)
Gonadosomatic index ( I G ) and germ cell numbers in seminiferous tubules were significantly reduced in triploid male catfish compared with diploids. Triploid females had lower I G than diploids, with atretic follicles in their ovaries during prespawning and spawning phases.

Frequency of cytochrome P 450 3A4 variant genotype in transplant population and lack of association with cyclosporin clearance - L. P. Rivory; H. Qin; S. J. Clarke; J. Eris; G. Duggin; E. Ray; R. J. Trent; J. F. Bishop (European Journal of Clinical Pharmacology, 2000)

A rare case of two malignancies: Carcinoma of the breast and uterine cervix - A. Ray; H. Mukundan; A. K. Bahadur; R. S. Rautela; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2000)

Physico-Chemical Quality of Drinking Water in Rohtas District of Bihar - D. Ray; R. Ravindar Rao; A. V. Bhoi; A. K. Biswas; A. K. Ganguly; P. B. Sanyal (Environmental Monitoring and Assessment, 2000)

Emplacement of Amba Dongar carbonatite-alkaline complex at Cretaceous/Tertiary boundary: Evidence from40Ar-39Ar chronology - Jyotiranjan S. Ray; Kanchan Pande; T. R. Venkatesan (Journal of Earth System Science, 2000)

Endangered Species Legislation beyond the Borders of the United States - Justina C. Ray; Joshua R. Ginsberg (Conservation Biology, 1999)
Note: This month's “Issues in International Conservation” was guest edited by Justina Ray who, with Associate Editor Joshua Ginsberg, presents an overview of some global trends in endangered species legislation.

Comparison of MPTP-induced changes in spontaneous neuronal discharge in the internal pallidal segment and in the substantia nigra pars reticulata in primates - T. Wichmann; Hagai Bergman; Philip A. Starr; Mahlon R. DeLong; Ray L. Watts; T. Subramanian (Experimental Brain Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

IGS/BIPM Time Transfer Pilot Project - Jim R. Ray (GPS Solutions, 1999)

Studies on ‘zinc deficiency syndrome’ in Black Bengal goats (Capra hircus) fed with fodder (Andropogon gayanus) grown on soil treated with an excess of calcium and phosphorus fertilizer - S.K. Ray; R. Roychoudhury; S.K. Bandopadhyayi; S. Basu (Veterinary Research Communications, 1997)

Comparison of Colombian and Costa Rican Strains of Rice Hoja Blanca Tenuivirus - Joachim R. De Miranda; Bertha-Cecilia Ramirez; Miguel Mun~oz; Ivan Lozano; Ray Wu; Anne-Lise Haenni; Ana M. Espinoza; Lee A. Calvert (Virus Genes, 1997)

Studies on mercury-detoxicating enzymes from a broad-spectrum mercury-resistant strain ofFlavobacterium rigense - R. Gachhui; J. Chaudhuri; S. Ray; K. Pahan; A. Mandal (Folia Microbiologica, 1997)

Angular momentum of Arctic Ocean tides - R. D. Ray; B. F. Chao; Z. Kowalik; A. Y. Proshutinsky (Journal of Geodesy, 1997)

IIb trioctahedral chlorite from the Barberton greenstone belt: crystal structure and rock composition constraints with implications to geothermometry - Xiaogang Xie; Gary R. Byerly; Ray E. Ferrell Jr. (Contributions to Mineralogy and Petrology, 1997)

Case 25 application of the concentration parameter of seismoactive faults to Southern California - A. Zavyalov; R. E. Habermann; A. D. Zavyalov; Ray E. Habermann; Paul Reasenberg; Chen Yong (Pure and Applied Geophysics, 1997)

Effect of a growth hormone treatment on bone orthotropic elasticity in dwarf rats - Sean S. Kohles; Daniel A. Martinez; James R. Bowers; Arthur C. Vailas; Ray Vanderby (Annals of Biomedical Engineering, 1997)

Chemical and biological characterization of volatile components of environmental samples after fractionation by vacuum line cryogenic distillation - Ray L. Hanson; Alan R. Dahl; Simon J. Rothenberg; Janet M. Benson; Antone L. Brooks; John S. Dutcher (Archives of Environmental Contamination and Toxicology, 1985)

Effects of cadmium on yolk utilization, growth, and survival of Atlantic salmon alevins and newly feeding fry - R. H. Peterson; J. L. Metcalfe; S. Ray (Archives of Environmental Contamination and Toxicology, 1983)

Effects of copper on the sabellid polychaete,Eudistylia vancouveri. II. Copper accumulation and tissue injury in the branchial crown - James S. Young; Roy R. Adee; Irene Piscopo; Ray L. Buschbom (Archives of Environmental Contamination and Toxicology, 1981)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Summary of papers presented at The Potato Conference held at the Western Regional Research Laboratory, October 17 and 18, 1949 - R. Kunkel; W. T. Penzer; Paul P. Logan; Ray Kueneman; W. A. Scott (American Journal of Potato Research, 1950)